All-solid-state secondary battery
Patent Information
- Application Number
- CN202580026234.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-01
- Filing Date
- 2025-02-10
- Publication Date
- 2026-11-03
AI Technical Summary
Existing lithium batteries pose a risk of fire and explosion under short-circuit conditions, and their volume changes significantly during charging and discharging, resulting in poor charging and discharging characteristics.
The all-solid-state secondary battery structure is adopted, in which the negative electrode active material layer includes lithium silicon oxide and carbon materials, especially fibrous carbon materials, to improve charging and discharging characteristics, and the amorphization degree of lithium silicon oxide is improved by doping with magnesium or calcium to suppress volume change.
It improves the initial charge and discharge efficiency of all-solid-state secondary batteries, reduces irreversible capacity, enhances specific capacity and energy density, and improves volume stability and high-rate characteristics during charging and discharging.
Smart Images

Figure CN123036696A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to all-solid-state secondary batteries. Background Technology
[0002] Recently, in response to industrial demands, there has been active development of batteries with high energy density and high safety. For example, lithium batteries are used in various applications such as information devices, communication devices, and automobiles. Because automobiles affect personal safety, safety is also of paramount importance.
[0003] Lithium-ion batteries using liquid electrolytes have an increased risk of catching fire and / or exploding in the event of a short circuit. All-solid-state secondary batteries using solid electrolytes instead of liquid electrolytes have been proposed. Solid electrolytes are less likely to catch fire than liquid electrolytes.
[0004] By using a solid electrolyte instead of a liquid electrolyte, all-solid-state secondary batteries reduce the likelihood of fire or explosion. All-solid-state batteries offer improved safety. Summary of the Invention
[0005] Technical issues
[0006] On the one hand, an all-solid-state secondary battery is provided, which has increased specific capacity due to initial efficiency, suppressed volume change during charging and discharging, and improved charging and discharging characteristics by including a first negative electrode active material having lithium silicon oxide in the negative electrode active material layer.
[0007] Solution to the problem
[0008] According to an embodiment, an all-solid-state secondary battery is provided, comprising a positive electrode layer; a negative electrode layer; and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, wherein the positive electrode layer comprises a positive electrode current collector and a positive electrode active material layer on one surface of the positive electrode current collector, the negative electrode layer comprises a negative electrode current collector and a first negative electrode active material layer on one surface of the negative electrode current collector, the first negative electrode active material layer comprises a first negative electrode active material and a carbon-based material, and the first negative electrode active material comprises lithium silicon oxide.
[0009] The first negative electrode active material layer may further include a second negative electrode active material. Additionally, the carbon-based material may be a fibrous carbon material.
[0010] Beneficial effects of the invention
[0011] According to one aspect, the negative electrode active material layer includes a first negative electrode active material containing lithium-ionized silicon oxide and carbon-based materials, thereby providing an all-solid-state secondary battery with increased specific capacity due to initial efficiency, suppressed volume changes during charging and discharging, and improved charging and discharging characteristics. Attached Figure Description
[0012] Figures 1-12 This is a cross-sectional view of an all-solid-state secondary battery according to an illustrative embodiment.
[0013] <List of reference numerals for key components>
[0014] 1 all-solid-state secondary battery with 10 positive electrodes
[0015] 11 Positive electrode current collector; 12 Positive electrode active material layer
[0016] 20 Negative electrode 21 Negative electrode current collector
[0017] 22 First negative electrode active material layer 23 Thin film
[0018] 24 Second negative electrode active material layer 30 Solid electrolyte layer
[0019] 40, 40a, 40b First inactive component; 50 Second inactive component Detailed Implementation
[0020] Unless otherwise specified, all terms used in this disclosure (including technical and scientific terms) shall have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure pertains. Furthermore, terms defined in common dictionaries shall be interpreted as having the same meaning as they have in the relevant field and in the context of this disclosure, and shall not be interpreted in an idealized or overly formal sense.
[0021] Exemplary embodiments are described in this disclosure with reference to cross-sectional views, which are schematic illustrations of preferred embodiments. Therefore, variations in the illustrated shape are expected due to factors such as manufacturing techniques and / or tolerances. Consequently, the embodiments described in this disclosure should not be construed as limited to a specific shape of the region as illustrated in this disclosure, but rather include shape deviations, for example, due to manufacturing processes. For instance, a region illustrated or described as flat may generally have rough and / or non-linear characteristics. Furthermore, the illustrated sharp corners may be rounded. Therefore, the regions illustrated in the figures are schematic in nature, and their shapes are not intended to illustrate precise shapes of the regions, nor are they intended to limit the scope of the claims.
[0022] The inventive concept can be embodied in many different forms and should not be construed as being limited to the embodiments described in this disclosure. The provision of embodiments makes this disclosure thorough and complete, and is provided to fully convey the scope of the inventive concept to those skilled in the art. The same reference numerals refer to the same components.
[0023] It will be understood that when a component is referred to as "on" another component, it can be directly on the other component or an intermediary component can exist between them. In contrast, when a component is referred to as "directly on" another component, there is no intermediary component between them.
[0024] Although the terms “first,” “second,” “third,” etc., may be used in this disclosure to describe various components, elements, areas, layers, and / or portions, these components, elements, areas, layers, and / or portions should not be limited by these terms. These terms are used only to distinguish one component, element, area, layer, or portion from another component, element, area, layer, or portion. Therefore, without departing from the teachings of this disclosure, the first component, element, area, layer, or portion described below may be referred to as the second component, element, area, layer, or portion.
[0025] The terminology used in this disclosure is for the purpose of describing particular embodiments only and is not intended to limit the inventive concept. As used herein, the singular form is intended to include the plural form containing "at least one," unless the context clearly indicates otherwise. "At least one" should not be construed as limited to the singular. As used in this disclosure, the term "and / or" includes any and all combinations of one or more of the listed items. The terms "includes" and / or "including" as used in the detailed description indicate the presence of the described features, areas, integers, steps, operations, components, and / or elements, but do not exclude the presence or addition of one or more other features, areas, integers, steps, operations, components, elements, and / or groups thereof.
[0026] For ease of description, spatial relative terms such as “below,” “under,” “down,” “above,” “on,” and “above” are used herein to describe the relationship of one component or feature to another. It will be understood that, in addition to the orientations depicted in the figures, spatial relative terms are also intended to encompass different orientations of the device in use or operation. For example, if the device in the figures is flipped, a component described as “below” or “under” another component or feature would be oriented “above” the other component or feature. Thus, the exemplary term “below” can encompass both above and below orientations. The device may be oriented in other ways (rotated 90 degrees or in other orientations), and the spatial relative terms used in this disclosure may be interpreted accordingly.
[0027] "Group" refers to the group of elements in the periodic table according to the International Union of Pure and Applied Chemistry (IUPAC) classification system of Groups 1-18.
[0028] In this disclosure, "particle size" refers to the average diameter when the particle is spherical, and the average major axis length when the particle is non-spherical. Particle size can be measured using a particle size analyzer (PSA). "Particle size" refers to, for example, the average particle size. The "average particle size" can be, for example, D50, as the median particle size. D50 is the particle size corresponding to 50% of the cumulative volume, calculated from the smaller particle size side in a particle size distribution measured by laser diffraction. D90 is the particle size corresponding to 90% of the cumulative volume, calculated from the smaller particle size side in a particle size distribution measured by laser diffraction. D10 is the particle size corresponding to 10% of the cumulative volume, calculated from the smaller particle size side in a particle size distribution measured by laser diffraction.
[0029] In this disclosure, "metal" includes both metals in an elemental or ionic state and metalloids (such as silicon and germanium).
[0030] In this disclosure, "alloy" refers to a mixture of two or more metals.
[0031] In this disclosure, "electrode active material" refers to an electrode material capable of undergoing lithiation and delithiation, and "positive electrode active material" refers to a positive electrode material capable of undergoing lithiation and delithiation. In this disclosure, "negative electrode active material" refers to a negative electrode material capable of undergoing lithiation and delithiation, and "lithiation" and "to lithiate" refer to the process of adding lithium to the electrode active material.
[0032] In this disclosure, "delithiate" and "to delithiate" refer to the process of removing lithium from the electrode active material.
[0033] In this disclosure, “charge” and “to charge” refer to the process of providing electrochemical energy to the battery, and “discharge” and “to discharge” refer to the process of removing electrochemical energy from the battery.
[0034] In this disclosure, "positive electrode" and "positive electrode" refer to electrodes that undergo electrochemical reduction and lithiation during the discharge process, and "negative electrode" and "negative electrode" refer to electrodes that undergo electrochemical oxidation and delithiation during the discharge process.
[0035] In this disclosure, "aspect ratio" refers to the ratio (L / D) of the length of the major axis (e.g., length L) to the length of the minor axis (e.g., diameter D). In this disclosure, aspect ratio, length of the major axis, length of the minor axis, length, and diameter are all average values.
[0036] Although specific embodiments have been described, alternatives, modifications, variations, improvements, and substantial equivalents that are not presently foreseen or unforeseeable may occur to the applicant or those skilled in the art. Accordingly, the appended claims as filed and amendable are intended to cover all such alternatives, modifications, variations, improvements, and substantial equivalents.
[0037] Hereinafter, the all-solid-state secondary battery according to the exemplary embodiment will be described in more detail.
[0038] [All-solid-state secondary battery]
[0039] The all-solid-state secondary battery according to the embodiment includes a positive electrode layer; a negative electrode layer; and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, wherein the positive electrode layer includes a positive electrode current collector and a positive electrode active material layer on one surface of the positive electrode current collector, wherein the negative electrode layer includes a negative electrode current collector and a first negative electrode active material layer on one surface of the negative electrode current collector, wherein the first negative electrode active material layer includes a first negative electrode active material and a carbon-based material, and wherein the first negative electrode active material includes lithium silicon oxide.
[0040] In the present disclosure, the lithium silicon oxide is a compound represented by the following Formula 1.
[0041] Formula 1
[0042] Li x Si y O z
[0043] In Formula 1, 0<x≤4, 0<y≤5, and 0<z≤5.
[0044] According to an embodiment, in Formula 1, x is 1 to 4 or 2 to 4, y is 1 to 5, 1 to 4, 1 to 3, or 1 to 2, and z is 0.1 to 5, 0.1 to 4, 0.1 to 3, 0.1 to 2, 0.1 to 1.5, 0.5 to 1.5, 1.01 to 1.5, 1.02 to 1.2, 1.03 to 1.1, or 1.05 to 1.07.
[0045] According to another embodiment, in Formula 1, x is 1 to 4, y is 1 to 5, and z is 0.1 to 2.
[0046] In Formula 1, when the range of y exceeds 5, the portion occupied by irreversible capacity during reaction with lithium may increase, thereby reducing the initial efficiency.
[0047] According to the embodiment, the lithium silicon oxide may include Li-SiO z (0.5≤z≤2, 1≤z≤1.5, 1≤z≤1.3, 1≤z≤1.2, 1≤z≤1.1, or 1.07), Li₄SiO₄, or a combination thereof.
[0048] According to another embodiment, the lithium silicon oxide is Li2SiO3, Li2Si2O5, or a combination thereof.
[0049] The lithium silicon oxide may further include magnesium (Mg), calcium (Ca), or a combination thereof.
[0050] The lithium silicon oxide further comprising Mg, Ca, or a combination thereof may be represented by the following Formula 2.
[0051] Formula 2
[0052] Lix(MO) z1 (SiyO z )
[0053] In Formula 2,
[0054] 0<x≤4, 0<y≤5, 0<z≤5, 2.2≤z1≤5.5, and M is Mg, Ca, or a combination thereof.
[0055] According to an embodiment, in Formula 2, 0<x≤4, 0<y≤5, 2.2≤z1≤5.5, and M is Mg, Ca, or a combination thereof.
[0056] In Formula 2, x is 1 to 4 or 2 to 4, y is 1 to 5, 1 to 4, 1 to 3, or 1 to 2, and z is 0.1 to 5, 0.1 to 4, 0.1 to 3, 0.1 to 2, 0.1 to 1.5, 0.5 to 1.5, 1.01 to 1.5, 1.02 to 1.2, 1.03 to 1.1, or 1.05 to 1.07.
[0057] According to another embodiment, in Formula 2, 0.5≤z≤2, 1≤z≤1.5, 1≤z≤1.3, 1≤z≤1.2, 1≤z≤1.1, or 1≤z≤1.07.
[0058] The first negative electrode active material may further include, for example, Li4Si, Li2CO3, or a combination thereof.
[0059] When silicon oxide (SiO z ) is used as the negative electrode active material, because silicon oxide has low structural stability and low diffusion rate of Li atoms during charging and discharging, the all-solid secondary battery may have high irreversible capacity and short circuit life, and may exhibit reduced high-rate charge-discharge efficiency. However, compared with silicon oxide, during charging and discharging of the all-solid secondary battery, the lithium silicon oxide may improve initial charge-discharge efficiency, and may provide increased specific capacity through initial efficiency, suppressed volume change during charging and discharging, and improved charge and discharge characteristics.
[0060] Additionally, by doping Mg, Ca, or a combination thereof into lithium-modified silicon oxide (SiO2), z In this process, the amorphization of lithiated silicon oxide is improved, which inhibits the growth of Si metal aggregates that can form during the reduction of silicon oxide and improves the diffusion rate of Li atoms.
[0061] Based on 100 parts by weight of lithium silicon oxide, the doping content of doping elements Mg, Ca, or combinations thereof is 50 parts by weight or less, 10 parts by weight to 50 parts by weight, 10 parts by weight to 45 parts by weight, 15 parts by weight to 40 parts by weight, 15 parts by weight to 35 parts by weight, or 15 to 30 parts by weight. When the content of the doping element exceeds 50 parts by weight, the energy density of the all-solid-state secondary battery can be reduced, and the irreversible capacity of the all-solid-state secondary battery can be increased.
[0062] Methods for replacing lithium in the first negative electrode active material may include, but are not limited to, sputtering, electrochemical charging, grinding, etc., and any method in the art for replacing lithium in silicon oxide may be used. Because the first negative electrode active material is a lithium-substituted negative electrode active material, the initial charge-discharge efficiency of the all-solid-state secondary battery 1 including the first negative electrode active material can be further improved. As a result, due to the reduction in the irreversible capacity of the all-solid-state secondary battery 1, the specific capacity of the all-solid-state secondary battery 1 can be increased, and the energy density can be increased.
[0063] As described above, the first negative electrode active material layer comprises lithium silicon oxide, thereby improving the initial charge / discharge efficiency of the all-solid-state secondary battery during charging and discharging, and improving its high-speed charging and discharging characteristics. Because the all-solid-state secondary battery has improved initial charge / discharge efficiency, its irreversible capacity can be reduced. Consequently, the specific capacity of the all-solid-state secondary battery can be increased, and its energy density can be increased.
[0064] Because the first negative electrode active material layer includes lithium-substituted first negative electrode active material, the volume change of the first negative electrode active material layer during charging and discharging of the all-solid-state secondary battery can be mitigated. As a result, since the volume change of the negative electrode layer during charging and discharging of the all-solid-state secondary battery is mitigated, the high-rate characteristics and / or lifetime characteristics of the all-solid-state secondary battery can be improved. Furthermore, since the volume change of the negative electrode layer during charging and discharging of the all-solid-state secondary battery is mitigated, the thickness of the buffer member used to accommodate the volume change of the negative electrode layer can be reduced, or the buffer member can be omitted. As a result, the energy density of the all-solid-state secondary battery can be improved.
[0065] Because the first negative electrode active material layer includes the second negative electrode active material, the uniformity and / or lithium deposition rate during the charging process of the all-solid-state secondary battery can be improved. As a result, the lifetime characteristics and / or high-rate characteristics of the all-solid-state secondary battery can be improved.
[0066] The first negative electrode active material layer comprises a carbon-based material, and the carbon-based material provides a conductive path between the first negative electrode active material and / or the second negative electrode active material. Accordingly, the carbon-based material can more easily suppress the increase in internal resistance of the first negative electrode active material layer during charging and discharging of the all-solid-state secondary battery. As a result, the increase in internal resistance of the all-solid-state secondary battery can be suppressed. The carbon-based material can be a fibrous carbon-based material.
[0067] The first negative electrode active material layer may include a carbon-based material, which serves as a carrier / buffer between the first negative electrode active material and / or the second negative electrode active material. Accordingly, the carbon-based material can more easily mitigate the volume change of the first negative electrode active material layer during charging and discharging of the all-solid-state secondary battery. As a result, the volume change of the all-solid-state secondary battery during charging and discharging can be reduced. Here, the carbon-based material may be a fibrous carbon-based material.
[0068] Graphene shells can be formed on the surface of the active material of the first negative electrode. Graphene shells can be used as a carrier / buffer, thereby reducing volume changes during charging and discharging of all-solid-state secondary batteries.
[0069] refer to Figures 1-12 The all-solid-state secondary battery 1 includes a positive electrode layer 10; a negative electrode layer 20; and a solid electrolyte layer 30 between the positive electrode layer 10 and the negative electrode layer 20. The positive electrode layer 10 includes a positive electrode current collector 11 and a positive electrode active material layer 12 on one surface of the positive electrode current collector 11. The negative electrode layer 20 includes a negative electrode current collector 21 and a first negative electrode active material layer 22 on one surface of the negative electrode current collector 21. The first negative electrode active material layer 22 includes a first negative electrode active material and a carbon-based material. The first negative electrode active material contains lithium-modified silicon oxide.
[0070] The first negative electrode active material layer 22 may further contain a second negative electrode active material.
[0071] [Negative electrode layer]
[0072] [First negative electrode active material layer: First negative electrode active material]
[0073] refer to Figures 1-12 The negative electrode layer 20 includes a first negative electrode active material layer 22. The first negative electrode active material layer 22 includes a first negative electrode active material.
[0074] The first negative electrode active material comprises lithium-modified silicon oxide. Using such a first negative electrode active material can provide increased initial charge / discharge efficiency and / or increased discharge capacity.
[0075] The first negative electrode active material layer 22 may include a first negative electrode active material, and the first negative electrode active material may be in, for example, particulate form. The size of the first negative electrode active material in particulate form may be, for example, 20 μm or less, 15 μm or less, 10 μm or less, or 7 μm or less. The size of the first negative electrode active material in particulate form may be, for example, 0.1 μm to 20 μm, 0.5 μm to 20 μm, 1 μm to 20 μm, 1 μm to 15 μm, 1 μm to 10 μm, or 3 μm to 7 μm. Because the first negative electrode active material has a size within this range, it can more easily undergo reversible lithium absorption and / or desorption during charging and discharging. The size of the first negative electrode active material may be, for example, the average particle size of the first negative electrode active material. The average particle size of the first negative electrode active material may be, for example, the median diameter (D50) measured using a laser particle size distribution analyzer. The size of the first negative electrode active material may be measured, for example, by a laser particle size distribution analyzer, scanning electron microscope, etc.
[0076] The aspect ratio of the first negative electrode active material can be, for example, 5 or less, 4 or less, 3 or less, or 2 or less. The aspect ratio of the first negative electrode active material can be, for example, 1-5, 1-4, 1-3, or 1-2. Because the first negative electrode active material has an aspect ratio within this range, it can be more uniformly distributed within the first negative electrode active material layer 22. As a result, non-uniformity in the volume change of the first negative electrode active material during charging and discharging can be suppressed. The aspect ratio of the first negative electrode active material can be measured, for example, by scanning electron microscopy.
[0077] [First negative electrode active material layer: Second negative electrode active material]
[0078] refer to Figures 1-12 The negative electrode layer 20 includes a first negative electrode active material layer 22. The first negative electrode active material layer 22 may include a second negative electrode active material.
[0079] The second negative electrode active material can be, for example, a negative electrode material capable of forming an alloy with lithium or a negative electrode material capable of forming a compound with lithium. The second negative electrode active material differs from the first negative electrode active material. The size of the second negative electrode active material can, for example, be smaller than the size of the first negative electrode active material. The size of the second negative electrode active material can be, for example, 60% or less, 40% or less, 20% or less, or 10% or less of the size of the first negative electrode active material.
[0080] The first negative electrode active material layer 22 may include a second negative electrode active material, and the second negative electrode active material may be, for example, in particulate form. The size of the second negative electrode active material in particulate form may be, for example, less than 1 μm, 500 nm or less, 300 nm or less, or 100 nm or less. The size of the second negative electrode active material in particulate form may be, for example, 10 nm to less than 1 μm, 10 nm to 900 nm, 10 to 700 nm, 10 nm to 500 nm, 10 nm to 300 nm, 10 nm to 200 nm, or 10 nm to 100 nm. Because the second negative electrode active material has a size within this range, it can more easily undergo reversible lithium absorption and / or desorption during charging and discharging. The size of the second negative electrode active material may be, for example, the average particle size of the second negative electrode active material. The average particle size of the second negative electrode active material may be, for example, the median diameter (D50) measured using a laser particle size distribution analyzer.
[0081] The aspect ratio of the second negative electrode active material can be, for example, 5 or less, 4 or less, 3 or less, or 2 or less. The aspect ratio of the second negative electrode active material can be, for example, 1-5, 1-4, 1-3, or 1-2. Because the second negative electrode active material has an aspect ratio within this range, it can be more uniformly distributed within the first negative electrode active material layer 22. As a result, non-uniformity in the volume change of the second negative electrode active material during charging and discharging can be suppressed. The aspect ratio of the second negative electrode active material can be measured, for example, by scanning electron microscopy.
[0082] The second negative electrode active material included in the first negative electrode active material layer 22 includes, for example, a carbon-based negative electrode active material, a second metal-based negative electrode active material different from the first negative electrode active material, or a combination thereof.
[0083] Carbon-based negative electrode active materials include, for example, amorphous carbon, crystalline carbon, porous carbon, or combinations thereof. Amorphous carbon includes, for example, carbon black (CB), acetylene black (AB), furnace black (FB), Ketjen black (KB), graphene, etc., but is not limited to these, and any material classified as amorphous carbon in the art can be used. Amorphous carbon is carbon that has no crystallinity or very low crystallinity, and is different from crystalline carbon or graphitic carbon.
[0084] The active material for the carbon-based negative electrode can be, for example, porous carbon. The pore volume contained in the porous carbon can be, for example, 0.1 cc / g to 10.0 cc / g, 0.5 cc / g to 5 cc / g, or 0.1 cc / g to 1 cc / g. The average pore size contained in the porous carbon can be, for example, 1 nm to 50 nm, 1 nm to 30 nm, or 1 nm to 10 nm. The BET specific surface area of the porous carbon can be, for example, 100 m². 2 / g~3000m 2 / g.
[0085] The second metallic negative electrode active material may include, but is not limited to, at least one selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn), and may use any material in the art used as a metallic negative electrode active material or a quasi-metallic negative electrode active material (both of which form alloys or compounds with lithium). For example, nickel (Ni) does not form alloys with lithium and is therefore not a second metallic negative electrode active material.
[0086] The first negative electrode active material layer 22 comprises one type of second negative electrode active material or a mixture of various different second negative electrode active materials each selected from such second negative electrode active materials. For example, the first negative electrode active material layer 22 comprises only amorphous carbon, or comprises at least one selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). Optionally, the first negative electrode active material layer 22 comprises amorphous carbon and a mixture of at least one selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). The mixing ratio of the amorphous carbon and the gold, etc., by weight is, for example, 99:1 to 1:99, 10:1 to 1:2, 5:1 to 1:1, or 4:1 to 2:1, but is not necessarily limited to these ranges, and is selected according to the desired characteristics of the all-solid-state secondary battery 1. Because the active material of the second negative electrode has such a composition, the cycle characteristics of the all-solid-state secondary battery 1 can be further improved.
[0087] The first negative electrode active material layer 22 includes a second negative electrode active material, which may comprise, for example, a mixture of first particles composed of amorphous carbon and second particles composed of a second metallic negative electrode active material. The second metallic negative electrode active material includes, for example, gold (Au), platinum (Pt), palladium (Pd), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). Based on the total weight of the mixture, the content of the second particles may be 1 wt% to 99 wt%, 1 wt% to 60 wt%, 8 wt% to 60 wt%, 10 wt% to 50 wt%, 15 wt% to 40 wt%, or 20 wt% to 30 wt%. Because the second particles have a content within such a range, the cycle characteristics of the all-solid-state secondary battery 1 can be further improved, for example.
[0088] Optionally, the first negative electrode active material layer 22 includes a second negative electrode active material, and the second negative electrode active material may include, for example, a composite negative electrode active material. The composite negative electrode active material may include, for example, a carbon-based support and a third metal-based negative electrode active material supported on the carbon-based support. Because the composite negative electrode active material has such a structure, localization of the third metal-based negative electrode active material within the first negative electrode active material layer 22 is prevented, and a uniform distribution can be obtained. As a result, the cycle characteristics of the all-solid-state secondary battery 1 including the first negative electrode active material layer 22 are further improved.
[0089] The active material for the third metal-based negative electrode supported on a carbon-based carrier may include, for example, metals, metal oxides, metal-metal oxide complexes, or combinations thereof. Metals may include, for example, gold (Au), platinum (Pt), palladium (Pd), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), tellurium (Te), zinc (Zn), etc. Metal oxides may include, for example, gold (Au) oxide, platinum (Pt) oxide, palladium (Pd) oxide, silver (Ag) oxide, aluminum (Al) oxide, bismuth (Bi) oxide, tin (Sn) oxide, tellurium (Te) oxide, zinc (Zn) oxide, etc. x O y (0) <x≤2,0<y≤3)、Pt x O y (0) <x≤1,0<y≤2)、Pd x O y (0) <x≤1,0<y≤1)、Ag x O y (0) <x≤2,0<y≤1)、Al x O y (0) <x≤2,0<y≤3)、Bi x O y(0<x≤2, 0<y≤3), Sn x O y (0<x≤1, 0<y≤2), Te x O y (0<x≤1, 0<y≤3), Zn x O y (0<x≤1, 0<y≤1) or a combination thereof. The composite of metal and metal oxide may include, for example, a composite of Au and Au x O y (0<x≤2, 0<y≤3), a composite of Pt and Pt x O y (0<x≤1, 0<y≤2), a composite of Pd and Pd x O y (0<x≤1, 0<y≤1), a composite of Ag and Ag x O y (0<x≤2, 0<y≤1), a composite of Al and Al x O y (0<x≤2, 0<y≤3), a composite of Bi and Bi x Oy (0<x≤2, 0<y≤3), a composite of Sn and Sn x O y (0<x≤1, 0<y≤2), a composite of Te and Te x O y (0<x≤1, 0<y≤3), a composite of Zn and Zn x O y (0<x≤1, 0<y≤1) or a combination thereof.
[0090] The carbon-based support may be, for example, amorphous carbon. The amorphous carbon may be, for example, carbon black (CB), acetylene black (AB), furnace black (FB), Ketjen black (KB), graphene, activated carbon, and the like, but is not necessarily limited thereto, and any material classified as amorphous carbon in the art may be used. Amorphous carbon is carbon that has no crystallinity or very low crystallinity, and is different from crystalline carbon or graphitic carbon.
[0091] The composite negative electrode active material can be, for example, in particulate form. The particle size of the composite negative electrode active material in particulate form can be, for example, 10 nm to 2 μm, 10 nm to 1 μm, 10 nm to 500 nm, 10 nm to 200 nm, or 10 nm to 100 nm. Because the composite negative electrode active material has a particle size within such a range, it further facilitates the reversible absorption and / or desorption of lithium during charging and discharging. The third metal-based negative electrode active material supported on a carbon-based support can also be, for example, in particulate form. The particle size of the third metal-based negative electrode active material can be, for example, 1 nm to 200 nm, 1 nm to 150 nm, 5 nm to 100 nm, or 10 nm to 50 nm. The carbon-based support can also be, for example, in particulate form. The particle size of the carbon-based support can be, for example, 10 nm to 2 μm, 10 nm to 1 μm, 10 nm to 500 nm, 10 nm to 200 nm, or 10 nm to 100 nm. Because the carbon-based support has a particle size within this range, it can be disposed more uniformly within the first negative electrode active material layer. The carbon-based support can be, for example, nanoparticles with a particle size of 500 nm or smaller. The particle sizes of the composite negative electrode active material, the third metal-based negative electrode active material, and the carbon-based support are, for example, average particle sizes. The average particle size can be, for example, the median diameter (D50) measured using a laser particle size distribution analyzer. Optionally, the average particle size can be determined automatically, for example, from an electron microscope image using software, or manually.
[0092] The first negative electrode active material layer 22 may include a first negative electrode active material and a second negative electrode active material, and the mixing ratio of the first negative electrode active material and the second negative electrode active material, by weight, may be 9:1 to 1:9, 8:2 to 2:8, 7:3 to 3:7, or 6:4 to 4:6. Because the first negative electrode active material and the second negative electrode active material have such a weight ratio within these ranges, the cycle characteristics of the all-solid-state secondary battery 1 can be further improved.
[0093] [First negative electrode active material layer: fibrous carbon material]
[0094] In addition to the first negative electrode active material and the second negative electrode active material, the first negative electrode active material layer 22 may also include a carbon-based material. The carbon-based material may include, for example, a fibrous carbon-based material.
[0095] The first negative electrode active material layer 22 may include, for example, a mixture of lithium-ionized silicon oxide and fibrous carbon material as the first negative electrode active material, a composite of lithium-ionized silicon oxide and fibrous carbon material, or a combination thereof. The first negative electrode active material layer 22 may include, for example, a mixture of fibrous carbon material and one or more first negative electrode active materials selected from the group consisting of silicon (Si), gold (Au), platinum (Pt), palladium (Pd), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). The mixing ratio of the fibrous carbon material and silicon, etc., by weight may be, for example, 99:1~1:99, 10:1~1:10, 1:1~1:9, 1:1~1:8, 1:1~1:7, 1:1~1:6, 1:1~1:5, 1:1~1:4, or 1:1~1:3, but is not necessarily limited to these ranges and may be selected according to the desired characteristics of the all-solid-state secondary battery 1. Because of the composition of fibrous carbon materials and negative electrode active materials, the cycle characteristics of the all-solid-state secondary battery 1 can be further improved.
[0096] The first negative electrode active material layer 22 may include, for example, a mixture of first particles composed of a first negative electrode active material and second particles composed of fibrous carbon material. The first particles may be, for example, lithium-modified silicon oxide particles. Based on the total weight of the mixture, the content of the second particles may be, for example, 1 wt% to 30 wt%, 1 wt% to 25 wt%, 1 wt% to 20 wt%, 1 wt% to 15 wt%, or 1 wt% to 10 wt%. Because the fibrous carbon material has a content within such a range, the cycle characteristics of the all-solid-state secondary battery 1 may be further improved, for example.
[0097] The size of the second negative electrode active material can be, for example, smaller than the length of the fibrous carbon material. Because the length of the fibrous carbon material is greater than the size of the second negative electrode active material, the fibrous carbon material can act as a carrier and / or buffer between multiple second negative electrode active materials. The fibrous carbon material disposed between multiple second negative electrode active materials effectively alleviates stress caused by volume changes in the second negative electrode active materials due to lithium deposition and / or dissolution during charging and discharging. As a result, volume changes in the first negative electrode active material layer 22 during charging and discharging can be more effectively suppressed. The ratio of the size of the second negative electrode active material to the length of the fibrous carbon material can be, for example, 1:10~1:2000, 1:10~1:1000, 1:10~1:500, 1:10~1:200, 1:10~1:100, 1:10~1:50, or 1:10~1:20. Because the ratio of the size of the active material of the second negative electrode to the length of the fibrous carbon material is within such a range, the cycle characteristics of the all-solid-state secondary battery 1 can be further improved, for example.
[0098] The fibrous carbon material can be, for example, a conductive carbon material. Because the fibrous carbon material is conductive, it can provide a conductive path within the first negative electrode active material layer 22. The fibrous carbon material can more effectively reduce the internal resistance of the first negative electrode active material layer 22. As a result, the cycle characteristics of the all-solid-state secondary battery 1 are improved. The first negative electrode active material layer 22 may not include any other carbon-based conductive material besides the fibrous carbon material. Because the first negative electrode active material layer 22 does not include any other carbon-based conductive material besides the fibrous carbon material, the energy density of the first negative electrode active material layer 22 can be further improved.
[0099] The aspect ratio of fibrous carbon materials can be, for example, 10 or greater, 20 or greater, 30 or greater, or 50 or greater. The aspect ratio of fibrous carbon materials can be, for example, 2000 or less, 1000 or less, 500 or less, 200 or less, or 100 or less. The aspect ratio of fibrous carbon materials can be, for example, 10~2000, 20~2000, 30~2000, or 50~2000. The aspect ratio of fibrous carbon materials can be, for example, 10~2000, 10~1000, 10~500, 10~200, 10~100, 10~50, or 10~20. The aspect ratio of fibrous carbon materials can be, for example, the ratio of the length of the major axis of the fibrous carbon material (i.e., the length of the fibrous carbon material) to the length of the minor axis perpendicular to the major axis (i.e., the diameter of the fibrous carbon material). Because the fibrous carbon material has an aspect ratio within this range, the conductive path of the fibrous carbon material inside the first negative electrode active material layer 22 can be made longer. The fibrous carbon material forms a three-dimensional conductive network in the first negative electrode active material layer 22, thereby more effectively reducing the internal resistance of the first negative electrode active material layer 22. As a result, the internal resistance of the all-solid-state secondary battery 1 is reduced. For example, the high-rate characteristics of the all-solid-state secondary battery 1 can be improved.
[0100] The fibrous carbon materials may include, for example, amorphous fibrous carbon materials, crystalline fibrous carbon materials, or combinations thereof. Since the fibrous carbon materials include amorphous fibrous carbon materials, side reactions between lithium and the fibrous carbon materials can be more effectively suppressed. Because the reversibility of the electrode reactions in the all-solid-state secondary battery 1 during charging and discharging is improved, the cycle characteristics of the all-solid-state secondary battery 1 can be improved.
[0101] The diameter of the fibrous carbon material can be, for example, 50 nm or less, 30 nm or less, 20 nm or less, or 10 nm or less. The diameter of the fibrous carbon material can also be, for example, 1 nm to 50 nm, 1 nm to 30 nm, or 1 nm to 10 nm. Because the fibrous carbon material has a diameter within this range, the internal resistance of the first negative electrode active material layer 22 can be effectively reduced, and the fibrous carbon material can be easily dispersed in solvents and / or slurries during the fabrication of the first negative electrode active material layer 22.
[0102] The length of fibrous carbon materials can be, for example, 1000 μm or less, 100 μm or less, 50 μm or less, 10 μm or less, 5 μm or less, 2 μm or less, 1 μm or less, 500 nm or less, or 300 nm or less. The length of fibrous carbon materials can also be, for example, 100 nm to 1000 μm, 100 nm to 500 μm, 100 nm to 100 μm, 100 nm to 50 μm, 100 nm to 10 μm, 100 nm to 5 μm, 100 nm to 2 μm, 100 nm to 1 μm, 100 nm to 500 nm, or 100 nm to 300 nm. The length of the fibrous carbon material can be, for example, 500 nm to 1000 μm, 500 nm to 500 μm, 500 nm to 100 μm, 500 nm to 50 μm, 500 nm to 10 μm, 1 μm to 10 μm, or 2 μm to 8 μm. The increased length of the fibrous carbon material reduces the internal resistance of the electrode.
[0103] Fibrous carbon materials may include, for example, fibrous carbon nanostructures. Fibrous carbon nanostructures may include, for example, carbon nanofibers, carbon nanotubes, carbon nanoribbons, or combinations thereof.
[0104] Carbon nanotubes may include, for example, primary carbon nanotube structures, secondary carbon nanotube structures formed by the aggregation of multiple primary carbon nanotube particles, or combinations thereof.
[0105] The primary structure of carbon nanotubes is a single carbon nanotube unit. A carbon nanotube unit is a graphite sheet in the form of a cylinder with a diameter of nanometer size and an sp2 bond structure. Depending on the angle of curvature and structure of the graphite sheet, the carbon nanotube unit can exhibit conductive or semiconductor properties. Based on the number of bonds forming the walls, carbon nanotube units can be classified into single-walled carbon nanotubes (SWCNTs), double-walled carbon nanotubes (DWCNTs), multi-walled carbon nanotubes (MWCNTs), etc. The thinner the wall thickness of the carbon nanotube unit, the lower the electrical resistance.
[0106] The primary structure of carbon nanotubes can include, for example, single-walled carbon nanotubes (SWCNTs), double-walled carbon nanotubes (DWCNTs), and multi-walled carbon nanotubes (MWCNTs), or combinations thereof. The diameter of the primary structure of carbon nanotubes can be, for example, 1 nm or greater, or 2 nm or greater. The diameter of the primary structure of carbon nanotubes can be, for example, 20 nm or less, or 10 nm or less. The diameter of the primary structure of carbon nanotubes can be, for example, 1 nm to 20 nm, 1 nm to 15 nm, or 1 nm to 10 nm. The length of the primary structure of carbon nanotubes can be, for example, 100 nm or greater, or 200 nm or greater. The length of the primary structure of carbon nanotubes can be, for example, 2 μm or less, 1 μm or less, 500 nm or less, or 300 nm or less. The length of the primary structure of carbon nanotubes can be, for example, 100 nm to 2 μm, 100 nm to 1 μm, 100 nm to 500 nm, 100 nm to 400 nm, 100 nm to 300 nm, or 200 nm to 300 nm. The diameter and length of the primary structure of carbon nanotubes can be measured from scanning electron microscopy (SEM) or transmission electron microscopy (TEM) images. Alternatively, the diameter and / or length of the primary structure of carbon nanotubes can be measured by laser diffraction methods.
[0107] The secondary structure of carbon nanotubes is formed by aggregating the primary structure of carbon nanotubes, resulting in a bundle-type or rope-type structure, either wholly or partially. The secondary structure can include, for example, bundle-type carbon nanotubes, rope-type carbon nanotubes, or combinations thereof. The diameter of the secondary structure can be, for example, 2 nm or greater, or 3 nm or greater. Alternatively, the diameter can be, for example, 50 nm or less, 30 nm or less, 20 nm or less, or 10 nm or less. Another possible diameter range is 2 nm to 50 nm, 2 nm to 30 nm, or 2 nm to 20 nm. The length of the secondary structure can be, for example, 500 nm or greater, 700 nm or greater, 1 μm or greater, or 10 μm or greater. Finally, the length can be, for example, 1000 μm or less, 500 μm or less, or 100 μm or less. The length of the carbon nanotube secondary structure can be, for example, 500 nm to 1000 μm, 500 nm to 500 μm, 500 nm to 200 μm, 500 nm to 100 μm, 500 nm to 50 μm, 500 nm to 10 μm, 1 μm to 10 μm, or 2 μm to 8 μm. The diameter and length of the carbon nanotube secondary structure can be measured from scanning electron microscopy (SEM) images or optical microscopy. Alternatively, the diameter and / or length of the carbon nanotube secondary structure can be measured by laser diffraction.
[0108] The secondary structure of carbon nanotubes can be dispersed, for example, in a solvent, to convert it into a primary structure of carbon nanotubes, and then used in the fabrication of the first negative electrode active material layer 22.
[0109] [First negative electrode active material layer: binder]
[0110] The first negative electrode active material layer 22 may further include a binder.
[0111] Because the binder bonds the first negative electrode active material, the second negative electrode active material, and the fibrous carbon material, it can more effectively suppress the breakage of the conductive path between the first negative electrode active material and the fibrous carbon material caused by volume changes of the first negative electrode active material during lithium deposition and / or dissolution during charging and discharging. This can suppress the non-uniformity of the electrode reaction in the all-solid-state secondary battery 1.
[0112] The binder can improve the bonding strength between the first negative electrode active material layer 22 and the solid electrolyte layer 30, or between the first negative electrode active material layer 22 and the negative electrode current collector 21. For example, the binder can improve the wettability between the first negative electrode active material layer 22 and the solid electrolyte layer 30, or between the first negative electrode active material layer 22 and the negative electrode current collector 21. Accordingly, the binder can more effectively reduce the increase in interfacial resistance caused by void formation between the first negative electrode active material layer 22 and the solid electrolyte layer 30, or between the first negative electrode active material layer 22 and the negative electrode current collector 21. This can improve the cycle characteristics of the all-solid-state secondary battery 1.
[0113] When the first negative electrode active material layer does not include a binder, the surfaces of the solid electrolyte layer and / or negative electrode current collector will be exposed as the first negative electrode active material layer detaches from the solid electrolyte layer and / or negative electrode current collector. For example, the exposed negative electrode current collector can cause a short circuit. The cycle characteristics of the all-solid-state secondary battery will deteriorate.
[0114] The binder may be, for example, a polymer binder. The binder included in the first negative electrode active material layer 22 may be, for example, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, etc., but is not necessarily limited thereto, and any material used as a binder in the art may be used. The binder may consist of a single binder or multiple different binders. The binder may include, for example, a fluorinated binder.
[0115] Because the first negative electrode active material layer 22 includes a binder, it is stabilized on the negative electrode current collector 21. Furthermore, despite volume changes and / or relative positional changes in the first negative electrode active material layer 22 during charging and discharging processes, breakage of the first negative electrode active material layer 22 is suppressed. For example, when the first negative electrode active material layer 22 does not include a binder, it can easily separate from the negative electrode current collector 21. When the first negative electrode active material layer 22 detaches from the negative electrode current collector 21, the exposed portion of the current collector 21 comes into contact with the solid electrolyte layer 30, thereby increasing the likelihood of a short circuit. The first negative electrode active material layer 22 is manufactured, for example, by coating the negative electrode current collector 21 with a slurry in which the materials constituting the first negative electrode active material layer 22 are dispersed and then drying the slurry. By including a binder in the first negative electrode active material layer 22, stable dispersion of the negative electrode active material and fibrous carbonaceous materials in the slurry is possible. For example, when the paste is applied to the negative electrode current collector 21 by screen printing, screen clogging (e.g., clogging caused by aggregates of negative electrode active material) can be suppressed.
[0116] Based on 100 parts by weight of the mixture of the first negative electrode active material and the second negative electrode active material, the binder content can be 0.1 to 20 parts by weight, 0.1 to 15 parts by weight, 1 to 10 parts by weight, or 5 to 10 parts by weight. By having a binder content within this range, the cycle characteristics of the all-solid-state secondary battery 1 can be further improved.
[0117] [First negative electrode active material layer: other additives]
[0118] The first negative electrode active material layer 22 may further include additives used in conventional all-solid-state secondary batteries 1, such as fillers, coating agents, dispersants, ion-conducting additives, etc.
[0119] [Negative electrode layer: First negative electrode active material layer]
[0120] refer to Figures 1-12 The positive electrode layer 10 includes a positive electrode active material layer 12, and the negative electrode layer 20 includes a first negative electrode active material layer 22.
[0121] The initial charge capacity (B) of the first negative electrode active material layer 22 may be, for example, 75% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less of the initial charge capacity (A) of the positive electrode active material layer 12.
[0122] The ratio (B / A) of the initial charging capacity (B) of the first negative electrode active material layer 22 to the initial charging capacity (A) of the positive electrode active material layer 12 can be, for example, 0.01~0.75, 0.01~0.7, 0.01~0.6, 0.01~0.5, 0.01~0.6, 0.01~0.5, 0.01~0.4, 0.01~0.3, 0.01~0.2, or 0.01~0.1. The ratio (B / A) of the initial charging capacity (B) of the first negative electrode active material layer 22 to the initial charging capacity (A) of the positive electrode active material layer 12 can be, for example, 0.05~0.75, 0.1~0.7, 0.1~0.6, 0.2~0.6, 0.2~0.5, or 0.2~0.45. The initial charge capacity of the positive electrode active material layer 12 is determined by charging from a first open-circuit voltage to the maximum charge voltage (relative to Li / Li+). The initial charge capacity of the first negative electrode active material layer 22 is determined by charging from a second open-circuit voltage to 0.01 V (relative to Li / Li+). The maximum charge voltage is determined according to the type of positive electrode active material. The maximum charge voltage can be, for example, 1.5 V, 2.0 V, 2.5 V, 3.0 V, 3.5 V, 4.0 V, 4.2 V, or 4.3 V. For example, the maximum charge voltage of Li2S or Li2S complexes can be determined in the range of 2.5 V to 3.0 V (relative to Li / Li+). For example, the maximum charge voltage of lithium transition metal oxides can be determined in the range of 3.0 V to 4.5 V (relative to Li / Li+).
[0123] The initial charge capacity (mAh) of the positive electrode active material layer 12 is obtained by multiplying the specific charge capacity (mAh / g) of the positive electrode active material by the mass (g) of the positive electrode active material in the positive electrode active material layer 12. When several types of positive electrode active materials are used, the specific charge capacity × mass value is calculated for each positive electrode active material, and the sum of these values is the initial charge capacity of the positive electrode active material layer 12. The initial charge capacity of the first negative electrode active material layer 22 is also calculated in the same manner. The initial charge capacity of the first negative electrode active material layer 22 is obtained by multiplying the specific charge capacity (mAh / g) of the negative electrode active material by the mass of the negative electrode active material in the first negative electrode active material layer 22. When several types of negative electrode active materials are used, the specific charge capacity × mass value is calculated for each negative electrode active material, and the sum of these values is the initial charge capacity of the first negative electrode active material layer 22. The specific charge capacity of each of the positive and negative electrode active materials can be measured using an all-solid-state half-cell utilizing lithium metal as the counter electrode. The initial charge capacity of each of the positive electrode active material layer 12 and the first negative electrode active material layer 22 can be achieved using an all-solid-state half-cell at a constant current density (e.g., 0.1 mA / cm²). 2Direct measurement is performed at the positive electrode. Measurements can be taken from the first open-circuit voltage (OCV) to the maximum charging voltage (e.g., 3.0 V vs. Li / Li). + The operating voltage is measured. For the negative electrode, measurements can be performed against an operating voltage ranging from the second open-circuit voltage (OCV) to 0.01 V relative to the negative electrode (e.g., lithium metal). For example, an all-solid-state half-cell with a positive electrode active material layer can achieve an operating voltage of 0.1 mA / cm². 2 A constant current is applied from the first open-circuit voltage to 3.0 V. The all-solid-state half-cell with the first negative electrode active material layer can be charged at 0.1 mA / cm². 2 A constant current charges the circuit from the second open-circuit voltage to 0.01 V. The current density during constant current charging can be, for example, 0.2 mA / cm². 2 or 0.5 mA / cm 2 An all-solid-state half-cell with a positive electrode active material layer can be charged, for example, from a first open-circuit voltage to 2.5V, 2.0V, 3.5V, 4.0V, or 4.5V. The maximum charging voltage of the positive electrode active material layer can be determined by the maximum voltage of the battery that meets the safety conditions according to JISC8712:2015 of the Japanese Standards Institute.
[0124] When the initial charging capacity of the first negative electrode active material layer 22 is too small, the thickness of the first negative electrode active material layer 22 becomes very thin. This allows lithium dendrites formed between the first negative electrode active material layer 22 and the negative electrode current collector 21 during repeated charging and discharging processes to cause the first negative electrode active material layer 22 to collapse, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1. When the charging capacity of the first negative electrode active material layer 22 is excessively increased, the energy density of the all-solid-state secondary battery 1 decreases, and the internal resistance of the all-solid-state secondary battery 1 caused by the first negative electrode active material layer 22 increases, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1.
[0125] The thickness of the first negative electrode active material layer 22 can be, for example, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less of the thickness of the positive electrode active material layer 12. The thickness of the first negative electrode active material layer 22 can be, for example, 1% to 50%, 1% to 40%, 1% to 30%, 1% to 20%, or 1% to 10% of the thickness of the positive electrode active material layer 12. The thickness of the first negative electrode active material layer 22 can be, for example, 1 μm to 50 μm, 2 μm to 40 μm, 3 μm to 30 μm, 4 μm to 20 μm, or 5 μm to 20 μm. The thickness of the first negative electrode active material layer 22 can be, for example, 5 μm to 50 μm, 10 μm to 50 μm, 15 μm to 50 μm, 20 μm to 50 μm, or 25 μm to 50 μm. When the thickness of the first negative electrode active material layer 22 is too thin, lithium dendrites formed between the first negative electrode active material layer 22 and the negative electrode current collector 21 can cause the first negative electrode active material layer 22 to collapse, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1. When the thickness of the first negative electrode active material layer 22 is excessively increased, the energy density of the all-solid-state secondary battery 1 decreases, and the internal resistance of the all-solid-state secondary battery 1 caused by the first negative electrode active material layer 22 increases, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1. When the thickness of the first negative electrode active material layer 22 decreases, for example, the initial charging capacity of the first negative electrode active material layer 22 also decreases.
[0126] [Negative electrode layer: Second negative electrode active material layer]
[0127] refer to Figure 3 After charging, the all-solid-state secondary battery 1 may further include, for example, a second negative electrode active material layer 24 disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22. The second negative electrode active material layer 24 is a metal layer comprising lithium or a lithium alloy. The metal layer comprises lithium or a lithium alloy. Accordingly, because the second negative electrode active material layer 24 is a lithium-containing metal layer, it acts as, for example, a lithium reservoir. The lithium alloy may be, for example, Li-Al alloy, Li-Sn alloy, Li-In alloy, Li-Ag alloy, Li-Au alloy, Li-Zn alloy, Li-Ge alloy, Li-Si alloy, etc., but is not limited thereto, and any lithium alloy used in the art may be used. The second negative electrode active material layer 24 may be composed of one of these alloys or lithium, or may be composed of several types of alloys. The second negative electrode active material layer 24 may be, for example, a plate. During the charging process of the all-solid-state secondary battery 1, the second negative electrode active material layer 24 is deposited, for example, between the first negative electrode active material layer 22 and the negative electrode current collector 21.
[0128] The thickness of the second negative electrode active material layer 24 is not particularly limited, but can be, for example, 1 μm~200 μm, 1 μm~150 μm, 1 μm~100 μm, 1 μm~50 μm, 1 μm~30 μm, 1 μm~22 μm, or 1 μm~10 μm. When the thickness of the second negative electrode active material layer 24 is too thin, it is difficult to use it as a lithium storage tank. When the thickness of the second negative electrode active material layer 24 is too thick, the mass and volume of the all-solid-state secondary battery 1 increase, and the cycle characteristics of the all-solid-state secondary battery 1 may deteriorate.
[0129] The thickness of the second negative electrode active material layer 24 can, for example, be less than the thickness of the first negative electrode active material layer 22. The thickness of the second negative electrode active material layer 24 can be, for example, 70% or less, 60% or less, 50% or less, 40% or less, or 30% or less of the thickness of the first negative electrode active material layer 22. The thickness of the second negative electrode active material layer 24 can be, for example, 1% to 70%, 1% to 60%, 1% to 50%, 1% to 40%, or 1% to 30% of the thickness of the first negative electrode active material layer 22. As the thickness of the second negative electrode active material layer 24 becomes less than the thickness of the first negative electrode active material layer 22, volume changes during charging and discharging of the all-solid-state secondary battery can be suppressed. As a result, degradation caused by volume changes in the all-solid-state secondary battery can be suppressed.
[0130] Optionally, in the all-solid-state secondary battery 1, the second negative electrode active material layer 24 may be disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22, for example, before the assembly of the all-solid-state secondary battery 1. When the second negative electrode active material layer 24 is disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22 before the assembly of the all-solid-state secondary battery 1, the second negative electrode active material layer 24 is a metal layer including lithium and thus acts as a lithium reservoir. For example, a lithium foil may be disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22 before the assembly of the all-solid-state secondary battery 1.
[0131] When the second negative electrode active material layer 24 is deposited during charging after the assembly of the all-solid-state secondary battery 1, the second negative electrode active material layer 24 is not included during the assembly of the all-solid-state secondary battery 1, and therefore the energy density of the all-solid-state secondary battery 1 increases. During the charging of the all-solid-state secondary battery 1, charging exceeding the charging capacity of the first negative electrode active material layer 22 is performed. That is, the first negative electrode active material layer 22 is overcharged. In the initial stage of charging, lithium is absorbed into the first negative electrode active material layer 22. The negative electrode active material included in the first negative electrode active material layer 22 forms an alloy or compound with the lithium ions that have migrated from the positive electrode 10. When charging exceeding the capacity of the first negative electrode active material layer 22 is performed, lithium is deposited, for example, on the rear surface of the first negative electrode active material layer 22, that is, between the negative electrode current collector 21 and the first negative electrode active material layer 22, and a metal layer corresponding to the second negative electrode active material layer 24 is formed by the deposited lithium. The second negative electrode active material layer 24 is a metal layer mainly composed of lithium (i.e., metallic lithium). For example, this result is obtained when the negative electrode active material included in the first negative electrode active material layer 22 comprises a material that forms an alloy or compound with lithium. During discharge, lithium in the first negative electrode active material layer 22 and the second negative electrode active material layer 24 (i.e., the metal layer) is ionized and moves toward the positive electrode 10. Accordingly, lithium can be used as the negative electrode active material in the all-solid-state secondary battery 1. In addition, since the first negative electrode active material layer 22 covers the second negative electrode active material layer 24, the first negative electrode active material layer 22 serves as a protective layer for the second negative electrode active material layer 24 (i.e., the metal layer) and simultaneously suppresses the deposition and growth of lithium dendrites. Accordingly, short circuits and capacity degradation in the all-solid-state secondary battery 1 are suppressed, and as a result, the cycle characteristics of the all-solid-state secondary battery 1 are improved. Furthermore, when the second negative electrode active material layer 24 is charged after the assembly of the all-solid-state secondary battery 1, the negative electrode 20 (i.e., the negative electrode current collector 21 and the first negative electrode active material layer 22 and the region therebetween) is a lithium-free region that does not contain lithium (Li) in the initial state or in the state after the all-solid-state secondary battery 1 is fully discharged.
[0132] [Negative electrode layer: negative electrode current collector]
[0133] The negative electrode current collector 21 is composed of, for example, a material that does not react with lithium (i.e., a material that neither forms an alloy nor a compound). The material constituting the negative electrode current collector 21 may be, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), etc., but is not necessarily limited thereto, and any material used as an electrode current collector in the art may be used. The negative electrode current collector 21 may include one of the aforementioned metals, or may include an alloy or coating material of two or more metals. The negative electrode current collector 21 may be in the form of, for example, a plate or foil.
[0134] refer to Figure 2 The all-solid-state secondary battery 1 may further include a thin film 23 comprising elements capable of forming an alloy with lithium on one surface of the negative electrode current collector 21. The thin film 23 is disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22. The thin film 23 comprises, for example, elements capable of forming an alloy with lithium. Elements capable of forming an alloy with lithium may be, for example, gold, silver, zinc, tin, indium, silicon, aluminum, bismuth, etc., but are not necessarily limited thereto, and any element capable of forming an alloy with lithium in the art may be used. The thin film 23 is composed of one of these metals, or an alloy of several types of metals. Because the thin film 23 is disposed on one surface of the negative electrode current collector 21, the deposition form of the second negative electrode active material layer 24, for example, deposited between the thin film 23 and the first negative electrode active material layer 22, is further planarized, and the cycle characteristics of the all-solid-state secondary battery 1 can be further improved.
[0135] The thickness of the thin film 23 can be, for example, 1 nm to 800 nm, 10 nm to 700 nm, 50 nm to 600 nm, or 100 nm to 500 nm. When the thickness of the thin film 23 is less than 1 nm, it may be difficult to demonstrate the function of the thin film 23. When the thickness of the thin film 23 is too thick, the thin film 23 itself absorbs lithium, which reduces the amount of lithium deposited in the negative electrode, thereby reducing the energy density of the all-solid-state battery and the cycle characteristics of the all-solid-state secondary battery 1. The thin film 23 can be deposited on the negative electrode current collector 21 by, for example, vacuum deposition, sputtering, or coating, but is not limited to these methods, and any method in the relevant art capable of forming the thin film 23 can be used.
[0136] Although not shown in the accompanying drawings, the negative electrode current collector 21 may include, for example, a base film and a metal layer disposed on one or both surfaces of the base film. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may include, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or combinations thereof. The polymer may be an insulating polymer. Because the base film includes an insulating thermoplastic polymer, when a short circuit occurs, the base film softens or liquefies to cut off battery operation, thereby suppressing a rapid increase in current. The metal layer may include, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), or alloys thereof. The negative electrode current collector 21 may further include a metal chip and / or lead terminals. For a more detailed description of the base film, metal layer, metal chip, and lead terminals of the negative electrode current collector 21, refer to the positive electrode current collector 11 described below. Because the negative electrode current collector 21 has such a structure, the weight of the negative electrode can be reduced, thereby improving the energy density of the negative electrode and the all-solid-state secondary battery.
[0137] [Negative electrode layer: First inactive component]
[0138] refer to Figures 4-5 and Figures 8-12 The all-solid-state secondary battery 1 may further include a first inactive member 40, 40a or 40b disposed on at least one of the other surfaces of the negative electrode current collector 21 and the positive electrode current collector 11.
[0139] The first inactive component 40, 40a, or 40b may not include electrode active material. The first inactive component 40, 40a, or 40b may be, for example, an insulating component.
[0140] The first inactive component 40, 40a, or 40b may be made conductive by further including a conductive material. The first inactive component 40, 40a, or 40b may be made, for example, a flame-retardant inactive component by further including a flame-retardant material.
[0141] The first inactive member 40, 40a, or 40b may be, for example, an elastic member. The first inactive member 40, 40a, or 40b may be, for example, a porous elastic member. The first inactive member 40, 40a, or 40b may be, for example, an elastic member having at least one of porosity, electrical conductivity, and flame retardancy.
[0142] The first inactive component 40, 40a, or 40b provides a buffering function for the all-solid-state secondary battery 1. The first inactive component 40, 40a, or 40b provides, for example, stress relaxation and restoring force. The first inactive component 40, 40a, or 40b can effectively accommodate volume changes in the all-solid-state secondary battery 1 and apply a constant pressure to the all-solid-state secondary battery 1.
[0143] The first inactive component 40, 40a, or 40b may have an elastic modulus, for example, lower than that of the negative electrode current collector 21. Because the first inactive component 40, 40a, or 40b has an elastic modulus lower than that of the negative electrode current collector 21, it can more effectively accommodate the volume change 20 of the negative electrode layer during charging and discharging of the all-solid-state secondary battery 1. The first inactive component 50 can effectively alleviate the internal stress caused by the volume change of the all-solid-state secondary battery 1 during charging and discharging, thereby improving the cycle characteristics of the all-solid-state secondary battery 1.
[0144] The first inactive component 40, 40a, or 40b may be disposed, for example, on the negative electrode layer 20 of the all-solid-state secondary battery 1. During charging and discharging of the all-solid-state secondary battery 1, when the volume change of the negative electrode layer 20 is relatively greater than the volume change of the positive electrode layer 10 and the solid electrolyte layer 30, the first inactive component 40, 40a, or 40b is disposed adjacent to the negative electrode layer 20, thereby more effectively accommodating the volume change 20 of the negative electrode layer. In addition, since the first inactive component 40, 40a, or 40b applies a constant pressure to the negative electrode layer 20, uniform deposition of lithium metal in the negative electrode layer 20 can be induced, for example. Accordingly, the formation of defects in the all-solid-state secondary battery 1 due to non-uniform deposition of lithium metal can be more effectively prevented.
[0145] Optionally, the first inactive component 40, 40a, or 40b may be disposed on, for example, the positive electrode layer 10 of the all-solid-state secondary battery 1. Since the first inactive component 40, 40a, or 40b is disposed adjacent to the positive electrode layer 10, it can more effectively accommodate volume changes in the all-solid-state secondary battery 1. Furthermore, since the first inactive component 40, 40a, or 40b applies a constant pressure to the all-solid-state secondary battery 1, it can, for example, induce uniform deposition of lithium metal in the negative electrode layer 20. Accordingly, the formation of defects in the all-solid-state secondary battery 1 due to non-uniform deposition of lithium metal can be more effectively prevented.
[0146] The first inactive component 40, 40a, or 40b may comprise a polymer material, a rubber material, or a combination thereof. Because the first inactive component 40, 40a, or 40b comprises a polymer material, a rubber material, or a combination thereof, it may possess stress relaxation and restoring force. The polymer material may include, for example, polyurethane polymers, polyacrylic polymers, polystyrene polymers, polyester polymers, polyamide polymers, polyolefin polymers, or combinations thereof. The polymer material may be, for example, a polymer resin. The polymer material may be, for example, an adhesive resin. Rubber materials may include, for example, natural rubber (NR), butadiene rubber (BR), nitrile rubber, silicone rubber, isoprene rubber (IR), styrene-butadiene rubber (SBR), isoprene-butadiene rubber, styrene-isoprene-butadiene rubber, acrylonitrile-butadiene rubber (NBR), ethylene-propylene-diene rubber, halogenated butyl rubber, chloroprene (CR), halogenated isoprene rubber, halogenated isobutylene copolymer, chloroprene rubber, butyl rubber (IIR), halogenated isobutylene-p-methylstyrene rubber, or combinations thereof. Polyurethane polymers may include, for example, polyester polyurethanes, polyether polyurethanes, or combinations thereof. Polyacrylic acid polymers may include, for example, polyacrylates, polymethyl acrylate, polymethyl methacrylate, polymethyl methacrylate, or combinations thereof. Polystyrene polymers may include, for example, styrene-ethylene-butene copolymer (SEB), styrene-butadiene-styrene copolymer (SBS), hydrogenated products of SBS (styrene-ethylene-butene-styrene copolymer (SEBS)), styrene-isoprene-styrene copolymer (SIS), hydrogenated products of SIS (styrene-ethylene-propylene-styrene copolymer (SEPS)), styrene-isobutylene-styrene copolymer (SIBS), styrene-butadiene-styrene-butadiene (SBSB), styrene-butadiene-styrene-butadiene-styrene (SBSBS), polystyrene (PS), acrylonitrile-styrene copolymer (AS), acrylonitrile-butadiene-styrene copolymer (ABS), or combinations thereof. Polyester polymers may include, for example, polyethylene terephthalate, polybutylene terephthalate, or combinations thereof. Polyamide polymers may include, for example, polyamide 6, polyamide 11, polyamide 12, polyamide 66, polyamide 610, or combinations thereof.Polyolefin polymers may include, for example, polyethylene, polypropylene, ethylene-propylene copolymers, propylene-1-hexene copolymers, propylene-4-methyl-1-pentene copolymers, propylene-1-butene copolymers, ethylene-1-hexene copolymers, ethylene-4-methyl-pentene copolymers, ethylene-1-butene copolymers, 1-butene-1-hexene copolymers, 1-butene-4-methyl-pentene, ethylene-methacrylic acid copolymers, ethylene-ethyl methacrylate copolymers, ethylene-ethyl methacrylate copolymers, ethylene-butyl methacrylate copolymers, ethylene-methyl acrylate copolymers, ethylene-ethyl acrylate copolymers, ethylene-butyl acrylate copolymers, propylene-methacrylic acid copolymers, propylene-methyl methacrylate copolymers, propylene-ethyl methacrylate copolymers, propylene-butyl methacrylate copolymers, ethylene-vinyl acetate copolymers (EVA), polyolefins of propylene-vinyl acetate copolymers, or combinations thereof.
[0147] The first inactive component 40, 40a, or 40b may include, for example, porous foam, porous sponge, or a combination thereof. The first inactive component 40, 40a, or 40b may include, for example, porous foam sheets, porous sponge sheets, or a combination thereof. Because the first inactive component 40, 40a, or 40b has this form, it can simultaneously provide porosity and cushioning function. Porous foam may include, for example, closed-cell, open-cell, or a combination thereof. Porous sponge may include, for example, closed-cell, open-cell, or a combination thereof. Closed-cell refers to, for example, a pore or pore that is closed and not connected to the surrounding atmosphere. Open-cell refers to, for example, a pore or pore that is open and connected to the surrounding atmosphere. The first inactive component 40, 40a, or 40b may include, for example, closed-cell porous foam, open-cell porous foam, closed-cell porous sponge, open-cell porous sponge, or a combination thereof. Porous foam may simultaneously include, for example, closed-cell and open-cell structures. Porous sponge may simultaneously include, for example, closed-cell and open-cell structures.
[0148] The first inactive component 40, 40a, or 40b may include, for example, a conductive material. The conductive material may be, for example, graphite, carbon black, acetylene black, Ketjen black, Tenca black, carbon fiber, carbon nanotubes (CNTs), graphene, metal fibers, metal powder, etc. The content of the conductive material included in the first inactive component 40, 40a, or 40b may be, for example, 1 to 30 parts by weight, 1 to 20 parts by weight, 1 to 15 parts by weight, 1 to 10 parts by weight, 5 to 40 parts by weight, 5 to 30 parts by weight, or 5 to 35 parts by weight, relative to 100 parts by weight of the first inactive component 40, 40a, or 40b. Because the first inactive component 50 is conductive, it can be used as a negative electrode current collector 50.
[0149] The first inactive component 40, 40a, or 40b includes, for example, a matrix and a filler. The matrix includes, for example, a substrate and a reinforcing member. The matrix includes, for example, a fibrous substrate and a fibrous reinforcing member. Because the matrix includes a fibrous substrate, the matrix can be elastic. The fibrous substrate includes, for example, at least one selected from pulp fibers, insulating polymer fibers, and ion-conducting polymer fibers. Because the matrix includes a reinforcing member, the strength of the matrix is improved. The fibrous reinforcing member can be, for example, glass fiber, metal oxide fiber, ceramic fiber, etc. The fibrous reinforcing member can be, for example, a flame-retardant material. The filler can be, for example, a hygroscopic agent and / or a flame retardant. The filler can be, for example, a metal hydroxide with moisture adsorption properties. The metal hydroxide included in the filler can be, for example, Mg(OH)2, Fe(OH)3, Sb(OH)3, Sn(OH)4, Ti(OH)3, Zr(OH)4, Al(OH)3, or combinations thereof.
[0150] The thickness of the first inactive component 40, 40a, or 40b can be, for example, 1 μm to 300 μm, 10 μm to 200 μm, 10 μm to 100 μm, or 10 μm to 50 μm. When the thickness of the first inactive component 40, 40a, or 40b is too thin, it is difficult to provide the desired effect, and when the thickness of the first inactive component 40, 40a, or 40b is too thick, the energy density of the all-solid-state secondary battery 1 can be reduced. The shape of the first inactive component 40, 40a, or 40b is not particularly limited and can be selected according to the shape of the all-solid-state secondary battery 1. The first inactive component 40, 40a, or 40b can be, for example, in the form of a sheet, rod, or pad. The first inactive component 40, 40a, or 40b can be omitted, for example.
[0151] [Positive electrode layer]
[0152] [Positive electrode active material layer: positive electrode active material]
[0153] refer to Figures 1-12 The positive electrode layer 10 may include a positive electrode active material layer 12. The positive electrode active material layer 12 may include a positive electrode active material.
[0154] The positive electrode active material included in the positive electrode active material layer 12 is a positive electrode active material capable of reversibly absorbing and desorbing lithium ions. The positive electrode active material may include, for example, oxide-based positive electrode active materials, sulfide-based positive electrode active materials, or combinations thereof.
[0155] Oxide-based positive electrode active materials may include, for example, lithium transition metal oxides, metal oxides, or combinations thereof. Lithium transition metal oxides may include, for example, lithium cobalt oxide, lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium iron phosphate, or combinations thereof. Lithium oxides may include, for example, iron oxides, vanadium oxides, or combinations thereof.
[0156] Sulfide-based positive electrode active materials may include, for example, nickel sulfides, copper sulfides, Li2S, Li2S-containing complexes, or combinations thereof.
[0157] As an oxide-based positive electrode active material, for example, lithium can be used in combination with one or more metals selected from cobalt, manganese, nickel, and combinations thereof. Lithium-containing oxide-based positive electrode active materials may include, for example, compounds represented by any of the following formulas: Li a A 1-b B' b D2 (where 0.90≤a≤1 and 0≤b≤0.5); Li a E 1-b B' b O 2-c D c (where 0.90≤a≤1, 0≤b≤0.5 and 0≤c≤0.05); LiE 2-b B' b O 4-c D c (where 0 ≤ b ≤ 0.5 and 0 ≤ c ≤ 0.05); Li a Ni 1-b-c Co b B' c D α (where 0.90≤a≤1, 0≤b≤0.5 and 0≤c≤0.05, 0<α≤2); Li a Ni 1-b-c Co b B' c O 2-α F' α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni 1-b-c Co b B' c O 2-α F' α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni 1-b-c Mn b B' c D α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05 and 0<α≤2); Li a Ni 1-b-c Mn b B' c O 2-α F' α(where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni 1-b-c Mn b B' c O 2-α F' α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni b E c G d O2 (where 0.90≤a≤1, 0≤b≤0.9, 0≤c≤0.5, 0.001≤d≤0.1); Li a Ni b Co c Mn d G e O2 (where 0.90≤a≤1, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5 and 0.001≤e≤0.1); Li a NiG b O2 (where 0.90≤a≤1 and 0.001≤b≤0.1); Li a CoG b O2 (where 0.90≤a≤1 and 0.001≤b≤0.1); Li a MnG b O2 (where 0.90≤a≤1 and 0.001≤b≤0.1); Li a Mn2G b O4 (where 0.90≤a≤1 and 0.001≤b≤0.1); LiV2O5; LiI'O2; LiNiVO4; Li (3-f) J2(PO4)3 (0≤f≤2); Li (3-f) Fe2(PO4)3 (0≤f≤2); and LiFePO4.
[0158] In the formula representing the above compound, A is Ni, Co, Mn or a combination thereof; B' is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element or a combination thereof; D is O, F, S, P or a combination thereof; E is Co, Mn or a combination thereof; F' is F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; Q is Ti, Mo, Mn or a combination thereof; I' is Cr, V, Fe, Sc, Y or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu or a combination thereof. A compound in which a coating is added to the surface of the above compound may also be used, and a mixture of the above compound and the compound with a coating added may also be used. The coating added to the surface of the above compound includes, for example, a coating element compound which is an oxide of a coating element, a hydroxide thereof, an oxyhydroxide of a coating element, an oxycarbonate of a coating element, or a hydroxycarbonate of a coating element. The compound constituting such a coating is amorphous or crystalline. The coating element included in the coating is Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr or a mixture thereof. The method for forming the coating is selected within a range that does not adversely affect the physical properties of the positive electrode active material. The coating method is, for example, spray coating, dip coating, and the like. Since a specific coating method is content that can be well understood by those skilled in the art, a detailed description thereof will be omitted.
[0159] The oxide-based positive electrode active material may include, for example, lithium transition metal oxides represented by Formula 3 to Formula 10:
[0160] Formula 3
[0161] Li a Ni x Co y M z O 2-b A b
[0162] In Formula 3, 1.0≤a≤1.2, 0≤b≤0.2, 0.8≤x<1, 0≤y≤0.3, 0<z≤0.3, and x+y+z=1, M is manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B) or a combination thereof,
[0163] A is F, S, Cl, Br or a combination thereof,
[0164] Formula 4
[0165] LiNi x Co y Mnz O2
[0166] Formula 5
[0167] LiNi x Co y Al z O2
[0168] In Formula 4 to Formula 5, 0.8≤x≤0.95, 0≤y≤0.2, 0<z≤0.2, and x+y+z=1,
[0169] Formula 6
[0170] LiNi x Co y Mn z Al w O2
[0171] In Formula 6, 0.8≤x≤0.95, 0≤y≤0.2, 0<z≤0.2, 0<w≤0.2, and x+y+z+w=1,
[0172] Formula 7
[0173] Li a Co x M y O 2-b A b
[0174] In Formula 7, 1.0≤a≤1.2, 0≤b≤0.2, 0.9≤x≤1, 0≤y≤0.1, and x+y=1, M is manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B) or a combination thereof, and A is F, S, Cl, Br or a combination thereof,
[0175] Formula 8
[0176] Li a Ni x Mn y M' z O 2-b A b
[0177] In Formula 8, 1.0≤a≤1.2, 0≤b≤0.2, 0<x≤0.3, 0.5≤y<1, 0<z≤0.3, and x+y+z=1, M' is cobalt (Co), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B), or a combination thereof, and A is F, S, Cl, Br, or a combination thereof,
[0178] Formula 9
[0179] Li a M1 x M2 y PO 4-b X b
[0180] In Formula 9, 0.90≤a≤1.1, 0≤x≤0.9, 0≤y≤0.5, 0.9<x+y<1.1, 0≤b≤2, M1 is chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zirconium (Zr), or a combination thereof, M2 is magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), zinc (Zn), boron (B), niobium (Nb), gallium (Ga), indium (In), molybdenum (Mo), tungsten (W), aluminum (Al), silicon (Si), chromium (Cr), vanadium (V), scandium (Sc), yttrium (Y), or a combination thereof, and X is O, F, S, P, or a combination thereof.
[0181] Formula 10
[0182] Li a M3 z PO4
[0183] In Formula 10, 0.90≤a≤1.1, 0.9≤z≤1.1, and M3 is chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zirconium (Zr), or a combination thereof.
[0184] The oxide-based positive electrode active material may be covered with a coating. The coating may be any known coating for positive electrode active materials of all-solid secondary batteries. The coating may be, for example, Li2O-ZrO2 (LZO) and the like.
[0185] The size of the oxide-based positive electrode active material may be, for example, 0.1 μm to 30 μm, 0.5 μm to 20 μm, or 1 to 15 μm. The oxide-based positive electrode active material may be, for example, single-crystal particles or polycrystalline particles.
[0186] Sulfide-based positive electrode active materials may include, for example, Li2S-containing complexes. Li2S-containing complexes include, for example, complexes of Li2S and carbon, complexes of Li2S, carbon, and solid electrolytes, complexes of Li2S and solid electrolytes, complexes of Li2S and lithium salts, complexes of Li2S, lithium salts, and carbon, complexes of Li2S and metal carbides, complexes of Li2S, carbon, and metal carbides, complexes of Li2S and metal nitrides, complexes of Li2S, carbon, and metal nitrides, or combinations thereof.
[0187] Li₂S complexes with carbon include carbon. Carbon can be any carbon-containing material used in the art as a conductive material, for example. Carbon can be, for example, crystalline carbon, amorphous carbon, or a combination thereof. Carbon can be, for example, a calcined product of a carbon precursor. Carbon can be, for example, a carbon nanostructure. Carbon nanostructures can be, for example, one-dimensional carbon nanostructures, two-dimensional carbon nanostructures, three-dimensional carbon nanostructures, or a combination thereof. Carbon nanostructures can be, for example, carbon nanotubes, carbon nanofibers, carbon nanoribbons, carbon nanorods, graphene, graphene oxide (GO), reduced graphene oxide (rGO), graphene spheres (GB), or a combination thereof. Carbon can be, for example, porous carbon or non-porous carbon. Porous carbon can include, for example, periodic and regular two-dimensional or three-dimensional pores. Porous carbon can be, for example, carbon black, such as Ketjen black, acetylene black, Denca black, thermally cracked carbon black, or channel black; graphite; activated carbon; or a combination thereof. Carbon can be in the form of, for example, granular, flake, fibrous, etc., but is not limited thereto, and any material used in the art as carbon can be used. The method for preparing the Li2S-carbon complex can be a dry method, a wet method, or a combination thereof, but is not limited thereto. The method used in the art for preparing the Li2S-carbon complex can be, for example, grinding, heat treatment, deposition, etc., but is not limited thereto, and any method used in the art can be used.
[0188] The Li₂S, carbon, and solid electrolyte complex includes carbon and a solid electrolyte. For carbon, refer to the above description of the Li₂S and carbon complex. The solid electrolyte may be, for example, an amorphous solid electrolyte, and may be any material used in the art as an ion-conducting material. The solid electrolyte may be, for example, a solid-free electrolyte. The solid electrolyte may be, for example, a crystalline solid electrolyte, an amorphous solid electrolyte, or a combination thereof. The solid electrolyte may be, for example, a sulfide solid electrolyte, an oxide solid electrolyte, or a combination thereof. Sulfide solid electrolytes include, for example, Li, S, and P, and may optionally further include halogen elements. The sulfide solid electrolyte may be selected from the sulfide solid electrolytes used in the solid electrolyte layer. The sulfide solid electrolyte may have, for example, a density of 1 × 10⁻⁶ at room temperature. -5Sulfide solid electrolytes may include, for example, those selected from Li3PO4-Li2SO4, Li2S-P2S5, Li2S-P2S5-LiX (where X is a halogen element), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, and Li2S-P2S5-Z. m S n (where m and n are each positive numbers and Z is one of Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (where p and q are positive numbers and M is one of P, Si, Ge, B, Al, Ga, and In), Li 7-x PS 6-x Cl x (where 0≤x≤2), Li 7-x PS 6-x Br x (where 0≤x≤2) and Li 7-x PS 6-x I x One or more of the following (where 0 ≤ x ≤ 2). Oxide solid electrolytes include, for example, Li, O, and transition metal elements, and may optionally further include another element. Oxide solid electrolytes may, for example, have a concentration of 1 × 10⁻⁶ at room temperature (25 °C). -5 Solid electrolytes with an ionic conductivity of S / cm or higher. Oxide-based solid electrolytes may be selected from those used in the solid electrolyte layer. The solid electrolyte may be, for example, a mixture of sulfide-based solid electrolytes and lithium salts. For example, the solid electrolyte may be a mixture of Li3PO4-Li2SO4 and binary lithium salts, or a mixture of Li3PO4-Li2SO4 and ternary lithium salts.
[0189] Complexes of Li₂S with solid electrolytes may include solid electrolytes. For solid electrolytes, refer to the above-described complexes of Li₂S, carbon, and solid electrolytes.
[0190] Complexes of Li₂S and lithium salts may include lithium salt compounds. Lithium salt compounds, for example, do not include sulfur (S) atoms. Lithium salt compounds may be binary compounds, for example, composed of lithium and an element selected from groups 13-17 of the periodic table. Binary compounds may include, for example, at least one selected from LiF, LiCl, LiBr, LiI, LiH, Li₂S, Li₂O, Li₂Se, Li₂Te, Li₃N, Li₃P, Li₃As, Li₃Sb, LiI₃, and LiB₃. Lithium salt compounds may be ternary compounds, for example, composed of lithium and two elements selected from groups 13-17 of the periodic table. Ternary compounds may include, for example, at least one selected from Li₃OCl, LiPF₆, LiBF₄, LiSbF₆, LiAsF₆, LiClO₄, LiAlO₂, LiAlCl₄, LiNO₃, Li₂CO₃, LiBH₄, Li₂SO₄, Li₃BO₃, Li₃PO₄, Li₄NCl, Li₅NCl₂, and Li₃BN₂. Specifically, the lithium salt compound is at least one lithium halide compound selected from LiF, LiCl, LiBr, and LiI. The complex of Li₂S with a solid electrolyte may include a solid electrolyte. For the solid electrolyte, refer to the solid electrolyte used in the above-described complex of Li₂S, carbon, and a solid electrolyte. The complex of Li₂S with a solid electrolyte may include, for example, a complex of Li₂S with at least one lithium salt selected from LiF, LiCl, LiBr, LiI, LiH, Li₂S, Li₂O, Li₂Se, Li₂Te, Li₃N, Li₃P, Li₃As, Li₃Sb, LiI₃, and LiB₃.
[0191] Complexes of Li₂S, lithium salts, and carbon may include lithium salt compounds and carbon. For lithium salt compounds, refer to the above description of Li₂S and lithium salt complexes. For carbon, refer to the above description of Li₂S and carbon complexes.
[0192] Complexes of Li₂S and metal carbides may include metal carbides. The metal carbides may be, for example, two-dimensional metal carbides. Two-dimensional metal carbides may be, for example, MXene. Two-dimensional metal carbides are composed of, for example, M... n+1 C n T x (Where M is a transition metal, T is an end group, T is O, OH and / or F, n = 1, 2 or 3, and x is the number of end groups) represents a two-dimensional metal carbide, for example, Ti2CT. x (Ti0.5,Nb0.5)2CT x Nb2CT x V2CT x Ti3C2T x (V0.5,Cr0.5)3C2T x Ti3CNTx Ta4C3T x Nb4C3T x Or a combination thereof. The surface of two-dimensional metal carbides is terminated with O, OH and / or F.
[0193] In the complex of Li₂S, carbon, and metal carbides, for carbon, refer to the carbon in the Li₂S and carbon complex described above. For metal carbides, refer to the metal carbides in the Li₂S and metal carbide complex described above.
[0194] In Li₂S-metal nitride complexes, the metal nitrides can be, for example, two-dimensional metal nitrides. Two-dimensional metal nitrides are composed of, for example, M... n+1 N n T x (Where M is a transition metal, T is an end group, T is O, OH and / or F, n = 1, 2 or 3, and x is the number of end groups) represents the surface of two-dimensional metal nitrides terminated with O, OH and / or F.
[0195] In the complex of Li₂S, carbon, and metal nitride, for carbon, refer to the carbon in the Li₂S and carbon complex described above. For metal carbides, refer to the metal carbides in the Li₂S and metal carbide complex described above.
[0196] The Li2S-containing complex may further include, for example, a second fibrous sulfide-based solid electrolyte (not shown). The Li2S-containing complex may be a complex of Li2S and a second fibrous sulfide-based solid electrolyte.
[0197] Since the Li2S-containing complex further includes a second fibrous sulfide-based solid electrolyte, the degradation of the all-solid-state secondary battery can be further suppressed, and the cycle characteristics of the all-solid-state secondary battery can be further improved. The size of the second fibrous sulfide-based solid electrolyte can be smaller than that of the first fibrous sulfide-based solid electrolyte. The length and / or thickness of the second fibrous sulfide-based solid electrolyte can be 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less, respectively, of the length and / or thickness of the first fibrous sulfide-based solid electrolyte 100. The length and / or thickness of the second fibrous sulfide-based solid electrolyte can be 0.1% to 50%, 0.5% to 40%, 1% to 30%, 1% to 20%, or 1% to 10%, respectively, of the length and / or thickness of the first fibrous sulfide-based solid electrolyte 100. The second fibrous sulfide-based solid electrolyte can have, for example, the same shape as the first fibrous sulfide-based solid electrolyte but with a smaller size. Because the second fibrous sulfide-based solid electrolyte has such a reduced length and / or thickness, it can be readily distributed within the Li₂S-containing complex. This reduced length and / or thickness further suppresses degradation of the all-solid-state secondary battery and further improves its cycle characteristics.
[0198] The size of sulfide-based positive electrode active materials can be, for example, 0.1 μm to 50 μm, 0.5 μm to 30 μm, 0.5 μm to 20 μm, or 1 μm to 10 μm. The size of Li₂S can be, for example, 1 nm to 10 μm, 10 nm to 5 μm, 10 nm to 3 μm, or 10 nm to 1 μm. The size of Li₂S-containing complexes can be, for example, 0.1 μm to 50 μm, 0.5 μm to 30 μm, 0.5 μm to 20 μm, or 1 μm to 10 μm.
[0199] The shape of the positive electrode active material can be, for example, particulate, such as spherical or ellipsoidal. The particle size of the positive electrode active material is not particularly limited and is within the range suitable for positive electrode active materials in conventional all-solid-state secondary batteries. The content of the positive electrode active material in the positive electrode layer 10 is also not particularly limited and is within the range suitable for positive electrode layers in conventional all-solid-state secondary batteries. The content of the positive electrode active material included in the positive electrode active material layer 12 can be, for example, 10 wt% to 99 wt%, 10 wt% to 90 wt%, 10 wt% to 80 wt%, 10 wt% to 70 wt%, or 10 wt% to 50 wt% of the total weight of the positive electrode active material layer 12.
[0200] [Positive electrode active material layer: solid electrolyte]
[0201] The positive electrode active material layer 12 may, for example, further include a solid electrolyte. The solid electrolyte may be, for example, a sulfide-based solid electrolyte. The solid electrolyte included in the positive electrode layer 10 may be the same as or different from the solid electrolyte included in the solid electrolyte layer 30. For details of the solid electrolyte, refer to the section on solid electrolyte layer 30.
[0202] The solid electrolyte included in the positive electrode active material layer 12 may have a smaller D50 average particle size than the solid electrolyte included in the solid electrolyte layer 30. For example, the D50 average particle size of the solid electrolyte included in the positive electrode active material layer 12 may be 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, or 20% or less of the D50 average particle size of the solid electrolyte included in the solid electrolyte layer 30. The D50 average particle size may be, for example, the median particle size (D50). The median particle size (D50) may be, for example, the particle size corresponding to 50% of the cumulative volume calculated from the smaller particle size side in a particle size distribution measured by laser diffraction.
[0203] The content of solid electrolyte included in the positive electrode active material layer 12 may be, for example, 1 wt% to 40 wt%, 1 wt% to 30 wt%, 1 wt% to 20 wt%, or 1 wt% to 10 wt% of the total weight of the positive electrode active material layer 12.
[0204] [Positive electrode active material layer: conductive material]
[0205] The positive electrode active material layer 12 may further include a conductive material. The conductive material may be, for example, a carbon-based conductive material, a metallic conductive material, or a combination thereof. The carbon-based conductive material may be, for example, graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or a combination thereof, but is not limited thereto, and any material used in the art as a carbon-based conductive material may be used. The metallic conductive material may be metal powder, metal fiber, or a combination thereof, but is not limited thereto, and any material used in the art as a metallic conductive material may be used. The content of the conductive material included in the positive electrode active material layer 12 may be, for example, 1 wt% to 30 wt%, 1 wt% to 20 wt%, or 1 wt% to 10 wt% of the total weight of the positive electrode active material layer 12.
[0206] [Positive electrode active material layer: binder]
[0207] The positive electrode active material layer 12 may further include a binder. The binder may be, for example, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc., but is not limited thereto, and any material used as a binder in the art may be used. The content of the binder included in the positive electrode active material layer 12 may be, for example, 1 wt% to 10 wt% of the total weight of the positive electrode active material layer 12. The binder may be omitted.
[0208] [Positive electrode active material layer: other additives]
[0209] In addition to the positive electrode active material, solid electrolyte, binder and conductive material mentioned above, the positive electrode active material layer 12 may further include additives, such as fillers, coating agents, dispersants and ion-conducting additives.
[0210] The positive electrode active material layer 12 may include fillers, coating agents, dispersants, ion-conducting additives, etc., and may use known materials commonly used in electrodes of all-solid-state secondary batteries.
[0211] [Positive electrode layer: positive electrode current collector]
[0212] The positive electrode current collector 11 can be, for example, a plate or foil composed of indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or alloys thereof. The positive electrode current collector 11 may be omitted. The thickness of the positive electrode current collector 11 can be, for example, 1 μm to 100 μm, 1 μm to 50 μm, 5 μm to 25 μm, or 10 μm to 20 μm.
[0213] The positive electrode current collector 11 may include, for example, a base film and a metal layer disposed on one or both surfaces of the base film. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may include, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or combinations thereof. The base film may be, for example, an insulator. Because the base film comprises an insulating thermoplastic polymer, it can soften or liquefy to block battery operation when a short circuit occurs, thereby suppressing a rapid increase in current. The metal layer may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), or alloys thereof. The metal layer may act as an electrochemical fuse and melt under overcurrent to perform short-circuit protection. The limiting current and maximum current can be adjusted by adjusting the thickness of the metal layer. The metal layer may be electroplated or deposited on the base film. Because the thickness of the metal layer is reduced, the limiting current and / or maximum current of the positive electrode current collector 11 are reduced, thus improving the stability of the all-solid-state secondary battery under short-circuit conditions. Lead terminals can be added to the metal layer for external connection. The lead terminals can be welded to the metal layer or metal layer / base film laminate by ultrasonic welding, laser welding, spot welding, etc. During welding, the base film and / or metal layer can melt, electrically connecting the metal layer to the lead terminals. To more firmly weld the metal layer and lead terminals, a metal chip can be added between the metal layer and the lead terminals. The metal chip can be a sheet made of the same material as the metal layer. The metal chip can be, for example, metal foil, metal mesh, etc. The metal chip can be, for example, aluminum foil, copper foil, SUS foil, etc. After the metal chip is placed on the metal layer, the lead terminals can be welded to the metal chip / metal layer laminate or metal chip / metal layer / base film laminate by welding lead terminals to it. During soldering, the base film, metal layer, and / or metal chip can be melted, allowing the metal layer or metal layer / metal chip laminate to be electrically connected to the lead patch. The metal chip and / or lead patch can be added to a portion of the metal layer. The thickness of the base film can be, for example, 1 μm to 50 μm, 1.5 μm to 50 μm, 1.5 μm to 40 μm, or 1 μm to 30 μm. Because the base film has a thickness within such a range, the weight of the electrode assembly can be reduced more effectively. The melting point of the base film can be, for example, 100°C to 300°C, 100°C to 250°C, or less, or 100°C to 200°C. Because the base film has a melting point within such a range, it can melt during the soldering of the lead patch, thus easily bonding it to the lead patch. To improve the adhesion between the base film and the metal layer, surface treatments such as corona treatment can be applied to the base film.The thickness of the metal layer can be, for example, 0.01 μm to 3 μm, 0.1 μm to 3 μm, 0.1 μm to 2 μm, or 0.1 μm to μm. Because the metal layer has a thickness within this range, the stability of the electrode assembly can be ensured while maintaining conductivity. The thickness of the metal chip can be, for example, 2 μm to 10 μm, 2 μm to 7 μm, or μm to 6 μm. Because the metal chip has a thickness within this range, the connection between the metal layer and the lead terminals can be made easier. Because the positive electrode current collector 11 has this structure, the weight of the positive electrode can be reduced, and thus the energy density of the positive electrode and the all-solid-state secondary battery can be improved.
[0214] [Positive electrode layer: First inactive component]
[0215] refer to Figures 4-5 and Figures 8-12 The all-solid-state secondary battery 1 may further include a first inactive member 40, 40a or 40b disposed on at least one of the other surface of the negative electrode current collector 21 and the other surface of the positive electrode current collector 11.
[0216] For further specific details regarding the first inactive component 40, 40a, or 40b, refer to the first inactive component 40, 40a, or 40b of the negative electrode layer described above.
[0217] [Positive electrode layer: Second inactive component]
[0218] refer to Figures 6-12 The positive electrode layer 10 includes a positive electrode current collector 11 and a positive electrode active material layer 12 disposed on one surface of the positive electrode current collector 11. A second inactive member 50 is disposed on one side surface of the positive electrode layer 10.
[0219] refer to Figure 7 , Figure 9 and Figure 11 A second inactive component 50 is disposed on one side surface of the positive electrode active material layer 12 and between the solid electrolyte layer 30 and the positive electrode current collector 11 facing the solid electrolyte layer 30. The second inactive component 50 is not disposed on one side surface of the positive electrode current collector 11. (See reference...) Figure 6 , Figure 8 , Figure 10 and Figure 12A second inactive component 50 is disposed on one side surface of the positive electrode active material layer 12 and the positive electrode current collector 11. By including the second inactive component 50, cracking of the solid electrolyte layer 30 during the manufacture and / or charging and discharging of the all-solid-state secondary battery 1 is prevented, and thus the cycle characteristics of the all-solid-state secondary battery 1 are improved. In an all-solid-state secondary battery 1 without the second inactive component 50, non-uniform pressure is applied to the solid electrolyte layer 30 in contact with the positive electrode layer 10 during the manufacture and / or charging and discharging of the all-solid-state secondary battery 1, thereby generating cracks in the solid electrolyte layer 30, and increasing the possibility of short circuits due to lithium metal growth therethrough.
[0220] refer to Figures 6-12 In the all-solid-state secondary battery 1, the thickness of the second inactive component 50 may, for example, be greater than the thickness of the first negative electrode active material layer 22. The thickness of the second inactive component 50 may, for example, be greater than the thickness of the solid electrolyte layer 30.
[0221] refer to Figures 6-12 The second inactive component 50 surrounds the side surface of the positive electrode layer 10 and is in contact with the solid electrolyte layer 30. Because the second inactive component 50 surrounds the side surface of the positive electrode layer 10 and is in contact with the solid electrolyte layer 30, cracks generated in the solid electrolyte layer 30 not in contact with the positive electrode layer 10 due to pressure differences in the solid electrolyte layer 30 during the pressing process can be effectively suppressed. The second inactive component 50 surrounds the side surface of the positive electrode layer 10 and is separated from the negative electrode layer 20, more specifically, from the first negative electrode active material layer 22. The second inactive component 50 surrounds the side surface of the positive electrode layer 10, is in contact with the solid electrolyte layer 30, and is separated from the negative electrode layer 20. Accordingly, the possibility of a short circuit due to physical contact between the positive electrode layer 10 and the first negative electrode active material layer 22, or the possibility of a short circuit due to lithium overcharging, etc., is suppressed. Since the second inactive component 50 is disposed on one side surface of both the positive electrode active material layer 12 and the positive electrode current collector 11, the possibility of a short circuit due to contact between the positive electrode current collector 11 and the negative electrode layer 20 is more effectively suppressed.
[0222] refer to Figures 6-12The second inactive member 50 extends from one side surface of the positive electrode layer 10 to the end of the solid electrolyte layer 30. Because the second inactive member 50 extends to the end of the solid electrolyte layer 30, cracking at the end of the solid electrolyte layer 30 can be suppressed. The end of the solid electrolyte layer 30 is the outermost portion in contact with the side surface of the solid electrolyte layer 30. The second inactive member 50 extends to the outermost portion in contact with the side surface of the solid electrolyte layer 30. The second inactive member 50 is separate from the negative electrode layer 20, and more specifically, separate from the first negative electrode active material layer 22. The second inactive member 50 extends to the end of the solid electrolyte layer 30 but does not contact the negative electrode layer 20. The second inactive member 50, for example, fills the space extending from one side surface of the positive electrode layer 10 to the end of the solid electrolyte layer 30.
[0223] The area of the positive electrode active material layer 12 or the positive electrode layer 10 may be smaller than the area of the first negative electrode active material layer 22 or the negative electrode layer 20. The area of the positive electrode active material layer 12 or the positive electrode layer 10 may be smaller than the area of the solid electrolyte layer 30.
[0224] The second inactive component 50 can be, for example, a gasket. Using a gasket as the second inactive component 50 can effectively suppress cracks in the solid electrolyte layer 30 caused by pressure differentials during the pressing process.
[0225] For example, the second inactive member 50 has a single-layer structure. Alternatively, although not shown in the figures, the second inactive member 50 may have a multi-layer structure. The multi-layer structure may have, for example, two, three, or four layers, and by having a multi-layer structure, the physical properties of the second inactive member 50 can be controlled more precisely.
[0226] Although not shown in the accompanying drawings, a portion or all of the second inactive member 50 may be arranged to be spaced apart from the side surface of the positive electrode active material layer 12. By arranging a portion or all of the second inactive member 50 to be spaced apart from the side surface of the positive electrode active material layer 12, the manufacturing process of the all-solid-state secondary battery 1 can be made easier, and the manufacturing speed of the all-solid-state secondary battery 1 can be increased. By arranging a portion or all of the second inactive member 50 to be spaced apart from the side surface of the positive electrode active material layer 12, the lateral volume changes of the positive electrode active material layer 12 during charging and discharging can be more effectively accommodated, thereby further improving the lifetime characteristics of the all-solid-state secondary battery 1. The distance between the second inactive member 50 and the side surface of the positive electrode active material layer 12 is independently, for example, 0.1 μm to 10 mm, 1 μm to 1 mm, 1 μm to 500 μm, 1 μm to 100 μm, 1 μm to 50 μm, or 1 μm to 10 μm.
[0227] refer to Figures 6-12The second inactive component 50 may be selected from, for example, the materials used in the first inactive components 40, 40a, or 40b described above. For example, the second inactive component 50 may not include an electrode active material. The second inactive component 50 may be, for example, a flame-retardant inactive component, an electronically insulating inactive component, an ionically insulating inactive component, or an elastic inactive component.
[0228] [Solid electrolyte layer]
[0229] [Solid electrolyte layer: solid electrolyte]
[0230] refer to Figures 1-12 The all-solid-state secondary battery 1 includes a solid electrolyte layer 30 disposed between a positive electrode layer 10 and a negative electrode layer 20. The solid electrolyte layer 30 includes, for example, a solid electrolyte or a combination of a solid electrolyte and a gel electrolyte.
[0231] Solid electrolytes may include, for example, sulfide solid electrolytes, oxide solid electrolytes, polymer solid electrolytes, or combinations thereof.
[0232] Solid electrolytes can be, for example, sulfide-based solid electrolytes. Sulfide-based solid electrolytes can be selected from, for example, Li₂S-P₂S₅, Li₂S-P₂S₅-LiX (where X is a halogen element), Li₂S-P₂S₅-Li₂O, Li₂S-P₂S₅-Li₂O-LiI, Li₂S-SiS₂, Li₂S-SiS₂-LiI, Li₂S-SiS₂-LiBr, Li₂S-SiS₂-LiCl, Li₂S-SiS₂-B₂S₃-LiI, Li₂S-SiS₂-P₂S₅-LiI, Li₂S-B₂S₃, and Li₂S-P₂S₅-Z. m S n (where m and n are both positive numbers, and Z is one of Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (where p and q are both positive numbers, and M is one of P, Si, Ge, B, Al, Ga, or In), Li 7-x PS 6-x Cl x (where 0≤x≤2), Li 7-x PS 6-x Br x (where 0≤x≤2) and Li 7-x PS 6- x I xAt least one of the following (where 0 ≤ x ≤ 2). Sulfide-based solid electrolytes are prepared by treating raw materials (such as Li₂S or P₂S₅) using a melt-quenching method or a mechanical grinding method. Additionally, heat treatment can be performed after such treatment. The solid electrolyte can be amorphous, crystalline, or in a mixture thereof. Furthermore, the solid electrolyte can be, for example, a material that includes at least sulfur (S), phosphorus (P), and lithium (Li) as constituent elements in the aforementioned sulfide-based solid electrolyte materials. For example, the solid electrolyte can be a material comprising Li₂S-P₂S₅. When a material comprising Li₂S-P₂S₅ is used as a sulfide-based solid electrolyte material to form the solid electrolyte, the molar ratio of Li₂S to P₂S₅ can be, for example, in the range of approximately Li₂S:P₂S₅ = 20:80~90:10, 25:75~90:10, 30:70~70:30, or 40:60~60:40.
[0233] Sulfide solid electrolytes may include, for example, sulfide-germanium ore type solid electrolytes represented by the following formula 11:
[0234] Formula 11
[0235] Li + 12-n-x A n+ X 2- 6-x Y - x
[0236] In Equation 11, A is P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb or Ta, X is S, Se or Te, Y is Cl, Br, I, F, CN, OCN, SCN or N3, 1≤n≤5q and 0≤x≤2.
[0237] Sulfide solid electrolytes may include, for example, those selected from Li 7-x PS 6-x Cl x (0≤x≤2), Li 7-x PS 6-x Br x (0≤x≤2) and Li 7-x PS 6-x I x At least one of the following (0≤x≤2) silver-germanium sulfide-type compounds. Sulfide solid electrolytes may be silver-germanium sulfide-type compounds, for example, selected from at least one of Li6PS5Cl, Li6PS5Br and Li6PS5I.
[0238] The density of argyrocerium sulfide-type solid electrolytes can range from 1.5 g / cc to 2.0 g / cc. Because argyrocerium sulfide-type solid electrolytes have a density of 1.5 g / cc or greater, the internal resistance of all-solid-state secondary batteries is reduced, and the permeation of Li into the solid electrolyte layer can be effectively suppressed.
[0239] Oxide-based solid electrolytes can be, for example, Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (0) <x<2,0≤y<3)、BaTiO3、Pb(Zr,Ti)O3(PZT)、Pb 1-x La x Zr 1-y Ti y O3(PLZT) (0≤x<1, 0≤y<1), PB(Mg3Nb 2 / 3 )O3-PbTiO3 (PMN-PT), HfO2, SrTiO3, SnO2, CeO2, Na2O, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, Li3PO4, Li x Ti y (PO4)3(0 <x<2,0<y<3)、Li x Al y Ti z (PO4)3(0 <x<2,0<y<1,0<z<3)、Li 1+x+y (Al, Ga) x (Ti,Ge) 2-x Si y P 3-y O 12 (0≤x≤1 0≤y≤1), Li x La y TiO3 (0 <x<2,0<y<3)、Li2O、LiOH、Li2CO3、LiAlO2、Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2、Li 3+x La3M2O 12 (M = Te, Nb, or Zr, 0 ≤ x ≤ 10) or combinations thereof. Oxide solid electrolytes are manufactured, for example, by sintering.
[0240] Oxide-based solid electrolytes can be, for example, selected from Li7La3Zr2O 12 (LLZO) and Li 3+x La3Zr 2-a M a O12 A garnet-type solid electrolyte (M-doped LLZO, M=Ga, W, Nb, Ta or Al, 0<a<2, 0≤x≤10).
[0241] The polymer solid electrolyte may include, for example, a mixture of a lithium salt and a polymer, or a polymer having an ion-conductive functional group. The polymer solid electrolyte may be, for example, a polymer electrolyte that is in a solid state at 25°C and 1 atm. The polymer solid electrolyte may, for example, not include a liquid. The polymer solid electrolyte includes a polymer, where the polymer may be, for example, polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene oxide (PEO), poly(styrene-b-ethylene oxide) block copolymer (PS-PEO), poly(styrene-butadiene), poly(styrene-isoprene-styrene), poly(styrene-b-divinylbenzene) block copolymer, poly(styrene-ethylene oxide-styrene) block copolymer, polystyrene sulfonate (PSS), polyvinyl fluoride, poly(methyl methacrylate) (PMMA), polyethylene glycol (PEG), polyacrylonitrile (PAN), polytetrafluoroethylene (PTFE), poly(3,4-ethylenedioxythiophene) (PEDOT), polypyrrole (PPY), polyacrylonitrile (PAN), polyaniline, polyacetylene, Nafion, Aquivion, Flemion, Gore, Aciplex, Morgane ADP, sulfonated poly(ether ether ketone) (SPEEK), sulfonated poly(arylene ether ketone ketone sulfone) (SPAEKKS), sulfonated poly(aryl ether ketone) (SPAEK), poly[bis(benzimidazolylbenzoisoquinolinone)] (SPBIBI), poly(styrene sulfonate) (PSS), lithium 9,10-diphenylanthracene-2-sulfonate (DPASLi⁺) or a combination thereof, but is not limited thereto, and any polymer used for polymer electrolytes in the art may be used. The lithium salt may be any lithium salt that can be used as a lithium salt in the art. The lithium salt may be, for example, LiPF₆, LiBF₄, LiSbF₆, LiAsF₆, LiClO₄, LiCF₃SO₃, Li(CF₃SO₂)₂N, Li(FSO₂)₂N, LiC₄F₉SO₃, LiAlO₂, LiAlCl₄, LiN(C x F 2x+ 1SO₂)(C y F 2y+1SO2 (where x and y are each 1 to 20), LiCl, LiI, or mixtures thereof. The polymer included in the polymer solid electrolyte may be, for example, a compound comprising 10 or more, 20 or more, 50 or more, or 100 or more repeating units. The weight-average molecular weight of the polymer included in the polymer solid electrolyte may be, for example, 1000 Daltons or greater, 10,000 Daltons or greater, 100,000 Daltons or greater, or 1,000,000 Daltons or greater.
[0242] The gel electrolyte can be, for example, a polymer gel electrolyte. The gel electrolyte can, for example, have a gel state that does not contain a polymer.
[0243] Polymer gel electrolytes may, for example, comprise a liquid electrolyte and a polymer, or comprise an organic solvent having ionicly conductive functional groups and a polymer. Polymer gel electrolytes may be, for example, polymer electrolytes that are in a gel state at 25°C and 1 atm. Polymer gel electrolytes may, for example, be in a gel state excluding liquid. The liquid electrolyte used in polymer gel electrolytes may be, for example, a mixture of ionic liquid, lithium salt, and organic solvent; a mixture of lithium salt and organic solvent; a mixture of ionic liquid and organic solvent; or a mixture of lithium salt, ionic liquid, and organic solvent. The polymer used in polymer gel electrolytes may be selected from the polymers used in polymer solid electrolytes. The organic solvent may be selected from the organic solvents used in liquid electrolytes. Organic solvents may be, for example, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butyl carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-ethylene glycol dimethyl ether, sulfolane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, or mixtures thereof. Lithium salts may be selected from lithium salts used in polymeric solid electrolytes. Ionic liquids may refer to salts having a melting point at or near room temperature, consisting solely of ions, and being liquid at room temperature, or room temperature molten salts. Ionic liquids may include, for example, at least one selected from compounds including: a) at least one cation selected from ammonium, pyrrolidine, pyridinium, pyrimidine, imidazolium, piperidinium, pyrazolium, oxazoline, pyridazine, phosphonium, thioonium, triazolium, and mixtures thereof; and b) at least one anion selected from BF4-, PF6-, AsF6-, SbF6-, AlCl4-, HSO4-, ClO4-, CH3SO3-, CF3CO2-, Cl-, Br-, I-, SO4-, CF3SO3-, (FSO2)2N-, (C2F5SO2)2N-, (C2F5SO2)(CF3SO2)N-, and (CF3SO2)2N-. Polymer solid electrolytes may be formed, for example, by impregnation with a liquid electrolyte used in a secondary battery to form a polymer gel electrolyte. The polymer gel electrolyte may further comprise inorganic particles. The polymer included in the polymer gel electrolyte may be, for example, a compound comprising 10 or more, 20 or more, 50 or more, or 100 or more repeating units. The weight-average molecular weight of the polymer included in the polymer gel electrolyte may be, for example, 500 Daltons or greater, 1000 Daltons or greater, 10,000 Daltons or greater, 100,000 Daltons or greater, or 1,000,000 Daltons or greater.
[0244] [Solid electrolyte layer: binder]
[0245] The solid electrolyte layer 30 may include, for example, an adhesive. The adhesive included in the solid electrolyte layer 30 may be, for example, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc., but is not limited thereto, and any material used as an adhesive in the art may be used. The adhesive of the solid electrolyte layer 30 may be the same as or different from the adhesive included in the positive electrode active material layer 12 and the negative electrode active material layer 22. The adhesive may be omitted.
[0246] The content of the binder included in the solid electrolyte layer 30 relative to the total weight of the solid electrolyte layer 30 is 0.1 wt% to 10 wt%, 0.1 wt% to 5 wt%, 0.1 wt% to 3 wt%, 0.1 wt% to 1 wt%, 0 to 0.5 wt%, or 0 to 0.1 wt%.
[0247] The inventive concept will be described in more detail through the following embodiments and comparative examples. However, the embodiments are provided to illustrate the inventive concept, and the scope of the inventive concept is not limited thereto.
[0248] (Manufacturing of sulfide-based composite positive electrode active materials)
[0249] Preparation Example 1: Li2S-LiI-CNF Composite Positive Electrode Active Material
[0250] Li₂S and LiI were mixed at a weight ratio of 30:20. The mixture was mechanically ground using a ball mill to prepare the Li₂S-LiI composite. The grinding conditions were 25°C at 510 rpm for 10 hours.
[0251] The Li₂S-LiI composite and carbon nanofibers (CNF) were mixed at a weight ratio of 50:10. The mixture was mechanically milled using a ball mill to prepare the Li₂S-LiI-CNF composite. The milling conditions were 25°C at 510 rpm for 10 hours. The Li₂S-LiI-CNF composite was used as the active material for the composite positive electrode.
[0252] (Manufacturing of all-solid-state secondary batteries)
[0253] Example 1: Elastic sheet (50 μm) / Positive electrode layer (112 μm, NCA) / Solid electrolyte layer (30 μm) / Negative electrode layer (37 μm, Li-SiO) z (z=1.07) Particles:CNT=9:1 + binder)
[0254] (Fabrication of the positive electrode layer)
[0255] Preparation of LiNi coated with Li2O-ZrO2 (LZO) 0.8 Co 0.15 Al0.05 O2 (NCA) was used as the positive electrode active material. LZO-coated positive electrode active material was prepared according to the method disclosed in Korean Patent Publication No. 10-2016-0064942. Li6PS5Cl (D50 = 0.5 μm, crystalline) as a silage-germanium sulfide crystal was prepared as the solid electrolyte. Polytetrafluoroethylene (PTFE) binder was prepared as the binder. CNF was prepared as the conductive agent. A slurry obtained by mixing these materials with xylene solvent at a weight ratio of positive electrode active material:solid electrolyte:conductive agent:binder = 84:11:3:2 was molded into a sheet and then vacuum dried at 40°C for 8 hours to prepare a positive electrode sheet. The prepared positive electrode sheet was placed on the carbon layer of a positive electrode current collector consisting of an aluminum foil with a carbon layer coated on one surface, and hot-rolled at 85°C to prepare a positive electrode layer. The total thickness of the positive electrode layer was approximately 112 μm. The thickness of the positive electrode active material layer is approximately 92 μm, and the thickness of the carbon-coated aluminum foil is approximately 20 μm.
[0256] The initial charge capacity of the positive electrode layer is measured using the aforementioned half-cell. The initial charge capacity of the positive electrode active material layer is measured using the half-cell.
[0257] (Manufacturing of the negative electrode layer)
[0258] A SUS foil with a thickness of 10 μm was prepared as the negative electrode current collector. Li-SiO₂ with a D50 particle size of 4 μm was used as the first negative electrode active material. y (y=1.07). Li-SiO z (z=1.07) indicates it was purchased. Carbon nanotubes consist of primary and secondary structures. A primary structure is composed of a single carbon nanotube unit. The length of a carbon nanotube unit is 200 nm–300 nm, and its diameter is approximately 5 nm–10 nm. A secondary structure is formed by the aggregation of multiple carbon nanotube units. The length of a secondary structure is approximately 5 μm, and its diameter is approximately 40 nm.
[0259] 2 g of Li-SiO₂ with a weight ratio of 9:1 zA mixture of (z=1.07) particles and carbon nanotubes was placed in a container with 2 g of a mixture of carbon black (CB) and silver (Ag) in a weight ratio of 3:1, and 4 g of an NMP solution including 7 wt% PVDF binder (#9300 from Kureha Corporation) was added to prepare a mixed solution. The mixed solution was stirred to prepare a slurry while NMP was added little by little. The prepared slurry was coated onto an SUS substrate using a doctor blade coater, dried in air at 80°C for 10 minutes, and then vacuum dried at 40°C for 10 hours to prepare a laminate. The prepared laminate was cold-rolled to planarize its surface, thereby preparing a negative electrode with a first negative electrode active material layer / negative electrode current collector structure. The thickness of the first negative electrode active material layer was approximately 27 μm.
[0260] The initial charge capacity of the negative electrode was measured using the aforementioned half-cell. The initial charge capacity of the active material layer of the first negative electrode was also measured using a half-cell.
[0261] The ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer to the initial charge capacity (A) of the positive electrode active material layer is less than 0.5. The initial charge capacity of the positive electrode active material layer is determined by charging from the first open-circuit voltage to 4.25 V (relative to Li / Li). + The initial charge capacity of the first negative electrode active material layer is determined by charging from the second open-circuit voltage to 0.01 V (relative to Li / Li). + The ratio (B / A) of the initial charge capacity of the first negative electrode active material layer to the initial charge capacity (A) of the positive electrode active material layer was determined to be 0.5 in each of Examples 2-3 and Comparative Example 3, measured under the same conditions as in Example 1.
[0262] In Example 2 and Comparative Example 1, measured under the same conditions as in Example 1, the ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer to the initial charge capacity (A) of the positive electrode active material layer was 0.48 and 0.58, respectively.
[0263] (Manufacturing of solid electrolyte layer)
[0264] To the solid electrolyte (D) of Li6PS5Cl as a sulforaphite-germanium type crystal 50=3.0 μm, crystalline) An acrylic binder was added to 1.5 parts by weight relative to 98.5 parts by weight of solid electrolyte to prepare a mixture. Octyl acetate was added to the prepared mixture while stirring to prepare a slurry. The prepared slurry was coated onto a nonwoven fabric placed on a PET substrate using a doctor blade coater and dried in air at 80°C for 10 minutes to prepare a laminate. The prepared laminate was vacuum dried at 80°C for 2 hours to produce the solid electrolyte layer.
[0265] (Non-active component: elastic sheet)
[0266] A porous polyurethane foam sheet with a thickness of 25 μm was prepared as an elastic sheet.
[0267] (Manufacturing of all-solid-state secondary batteries)
[0268] A solid electrolyte layer is placed on the negative electrode, so that the first negative electrode active material layer is in contact with the solid electrolyte layer, and a positive electrode is placed on the solid electrolyte layer, so that the positive electrode active material layer is in contact with the solid electrolyte layer, thereby preparing a laminate.
[0269] The prepared laminate was subjected to plate pressing at 85°C and 500 MPa for 30 minutes. This pressing process sintered the solid electrolyte layer, thereby improving battery characteristics. The thickness of the sintered solid electrolyte layer was approximately 30 μm. The density of the Li6PS5Cl solid electrolyte, which is a sulforaphite-type crystal included in the sintered solid electrolyte layer, was 1.6 g / cc. The area of the solid electrolyte layer was the same as the area of the negative electrode. An elastic sheet was additionally disposed on the positive electrode current collector of the pressed laminate.
[0270] A laminate, further comprising an elastic sheet, is placed in a bag and vacuum-sealed to manufacture an all-solid-state secondary battery. A portion of the positive and negative current collectors extends to the outside of the sealed battery and serves as the positive and negative electrode terminals.
[0271] Example 2: Elastic sheet (50 μm) / Positive electrode layer (112 μm, NCA) / Solid electrolyte layer (30 μm) / Negative electrode layer (37 μm, Li-SiO) z (z=1.07) Particles:CNT=9:1 + binder):(Li-SiO z (z=1.07) Particles:Ag-C = 2:2 weight ratio)
[0272] The all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that the negative electrode layer was manufactured according to the method described below.
[0273] (Manufacturing of the negative electrode layer)
[0274] A 10 μm thick SUS foil was prepared as the negative electrode current collector. Li-SiO₂ with a D50 particle size of 4 μm was used. z (z=1.07) is used as the active material for the first negative electrode. Li-SiO z (z=1.07) Purchased from Aldrich. Carbon nanotubes consist of primary and secondary structures. The primary structure is composed of a single carbon nanotube unit. The length of each unit is 200 nm–300 nm, and the diameter is 5 nm–10 nm. The secondary structure is formed by the aggregation of multiple carbon nanotube units. The secondary structure is approximately 5 μm long and approximately 40 nm in diameter.
[0275] 2 g of Li-SiO₂ with a weight ratio of 9:1 z A mixture of (z=1.07) particles and carbon nanotubes was placed in a container with 2 g of a mixture of carbon black (CB) and silver (Ag) in a 3:1 weight ratio, and 4 g of an NMP solution including 7 wt% PVDF binder (#9300 from Kureha Corporation) was added to prepare a mixed solution. A slurry was prepared by stirring the mixed solution while NMP was added little by little. The prepared slurry was coated onto an SUS substrate using a doctor blade coater, dried in air at 80°C for 10 minutes, and then vacuum dried at 40°C for 10 hours to prepare a laminate. The prepared laminate was cold-rolled to planarize its surface, thereby preparing a negative electrode with a first negative electrode active material layer / negative electrode current collector structure. The thickness of the first negative electrode active material layer was approximately 27 μm.
[0276] The initial charge capacity of the negative electrode was measured using the aforementioned half-cell. The initial charge capacity of the active material layer of the first negative electrode was also measured using a half-cell.
[0277] The ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer to the initial charge capacity (A) of the positive electrode active material layer is less than 0.5. The initial charge capacity of the positive electrode active material layer is determined by charging from the first open-circuit voltage to 4.25 V (relative to Li / Li). + The initial charge capacity of the first negative electrode active material layer is determined by charging from the second open-circuit voltage to 0.01 V (relative to Li / Li). + The ratio (B / A) of the initial charge capacity of the first negative electrode active material layer to the initial charge capacity (A) of the positive electrode active material layer was less than 0.5, measured under the same conditions as in Example 1.
[0278] Example 3: Elastic sheet (50 μm) / Positive electrode layer (112 μm, NCA) / Solid electrolyte layer (30 μm) / Negative electrode layer (37 μm, Li-SiO) z (y=1.07) Particles:CNT=9:1 + binder):(Li-SiO z (z=1.07) Particles:Ag-loaded carbon black = 2:2 weight ratio)
[0279] The all-solid-state secondary battery was manufactured in the same manner as in Example 2, except that 2 g of carbon black loaded with silver particles obtained according to the process described below was used instead of 2 g of a mixture of carbon black and silver particles in a weight ratio of 3:1 as the second negative electrode active material.
[0280] (Manufacturing of carbon black supported on silver particles)
[0281] Carbon black was dispersed in a 1.0 M sulfuric acid solution, stirred for 2 hours, and then filtered and dried to prepare acid-treated carbon black.
[0282] 10 g of acid-treated carbon black was added to a mixed solvent of 1500 g distilled water, 1500 g ethanol, and 30 g glycerol, and stirred. Then, 2 g of AgNO3 was added and stirred again to prepare a mixed solution. The carbon black particle size was 80 nm. A reducing agent was added to the mixed solution to reduce silver ions, and the resulting particles were loaded onto the carbon black. The carbon black loaded with silver particles was filtered, rinsed, and dried to prepare a composite negative electrode active material. Scanning electron microscopy and XPS measurements confirmed that multiple silver-containing particles were loaded onto the carbon black particles. The silver-containing particles included silver particles, silver oxide (Ag₂O) particles, and composite particles of silver (Ag) and silver oxide (Ag₂O). The composite negative electrode active material (carbon black loaded with silver particles) contained 5 wt% silver particles. The average particle size of the silver particles was 10 nm.
[0283] Comparative Example 1: Elastic sheet (50 μm) / Positive electrode layer (112 μm, NCA) / Solid electrolyte layer (30 μm) / Negative electrode layer (37 μm, SiO) z (z=1.07) Particles:CNT=9:1 + binder)
[0284] The all-solid-state secondary battery was prepared in the same manner as in Example 1, except that the negative electrode layer was prepared according to the following method.
[0285] (Manufacturing of the negative electrode layer)
[0286] A 10 μm thick SUS foil was prepared as the negative electrode current collector. SiO₂ with a D50 particle size of 4 μm was used. z(z=1.07) is used as the active material for the first negative electrode. SiO z (z=1.07) Purchased from Aldrich. Carbon nanotubes consist of primary and secondary structures. The primary structure is composed of a single carbon nanotube unit. The length of each unit is 200 nm–300 nm, and its diameter is approximately 5 nm–10 nm. The secondary structure is formed by the aggregation of multiple carbon nanotube units. The secondary structure is approximately 5 μm long and has a diameter of approximately 40 nm.
[0287] 2 g of Li-SiO₂ with a weight ratio of 9:1 z A mixture of (z=1.07) particles and carbon nanotubes was placed in a container with 2 g of a mixture of carbon black (CB) and silver (Ag) in a 3:1 weight ratio. 4 g of an NMP solution including 7 wt% PVDF binder (#9300 from Kureha Company) was added to prepare a mixed solution. The mixed solution was stirred while NMP was added little by little to prepare a slurry. The prepared slurry was coated onto an SUS substrate using a doctor blade coater, dried in air at 80°C for 10 minutes, and then vacuum dried at 40°C for 10 hours to prepare a laminate. The prepared laminate was cold-rolled to planarize its surface, thereby preparing a negative electrode with a first negative electrode active material layer / negative electrode current collector structure. The thickness of the first negative electrode active material layer was approximately 27 μm.
[0288] Comparative Example 2: Elastic sheet (50 μm) / Positive electrode layer (112 μm, NCA) / Solid electrolyte layer (30 μm) / Negative electrode layer (37 μm, SiO) z (z=1.07) Particles:CNT=9:1 + binder (SiO) z (Particles:Ag-C = 2:2 by weight)
[0289] An all-solid-state secondary battery was prepared in the same manner as in Comparative Example 1, except that the negative electrode layer was prepared according to the following method.
[0290] (Manufacturing of the negative electrode layer)
[0291] A 10 μm thick SUS foil was prepared as the negative electrode current collector. SiO₂ with a D50 particle size of 4 μm was used. z (z=1.07) is used as the active material for the first negative electrode. SiO z(z=1.07) Purchased from Aldrich. Carbon nanotubes consist of primary and secondary structures. The primary structure is composed of a single carbon nanotube unit. The length of each unit is 200 nm–300 nm, and the diameter is approximately 5 nm–10 nm. The secondary structure is formed by the aggregation of multiple carbon nanotube units. The secondary structure is approximately 5 μm long and approximately 40 nm in diameter.
[0292] 2 g of SiO₂ with a weight ratio of 9:1 z A mixture of (z=1.07) particulates and carbon nanotubes was placed in a container with 2 g of a mixture of carbon black (CB) and silver (Ag) in a 3:1 weight ratio. 4 g of an NMP solution containing 7 wt% PVDF binder (#9300 from Kureha Company) was added to prepare a mixed solution. A slurry was prepared by stirring the mixed solution while NMP was added little by little. The prepared slurry was coated onto an SUS substrate using a doctor blade coater, dried in air at 80°C for 10 minutes, and then vacuum dried at 40°C for 10 hours to prepare a laminate. The prepared laminate was cold-rolled to planarize the surface, thereby preparing a negative electrode with a first negative electrode active material layer / negative electrode current collector structure. The thickness of the first negative electrode active material layer was approximately 27 μm.
[0293] The initial charge capacity of the negative electrode is measured using the aforementioned half-cell.
[0294] Comparative Example 3: Elastic sheet (100 μm) / Positive electrode layer (112 μm, NCA) / Solid electrolyte layer (30 μm) / Negative electrode layer (17 μm, Ag-C+ binder)
[0295] The all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that the negative electrode was manufactured by the method described below and the thickness of the elastic sheet was changed to 100 μm.
[0296] (Manufacturing of the negative electrode)
[0297] A 10 μm thick SUS foil was prepared as the negative electrode current collector. A mixture of 4 g of carbon black (CB) and silver (Ag) in a 3:1 weight ratio was placed in a container, and 4 g of an NMP solution including 7 wt% PVDF binder (#9300 from Kureha Company) was added to prepare a mixed solution. While gradually adding NMP to the prepared mixed solution, the solution was stirred to prepare a slurry. The prepared slurry was coated onto an SUS substrate using a doctor blade coater, dried in air at 80°C for 10 minutes, and then vacuum dried at 40°C for 10 hours to prepare a laminate. The prepared laminate was cold-rolled to planarize the surface, thereby preparing a negative electrode with a first negative electrode active material layer / negative electrode current collector structure. The thickness of the first negative electrode active material layer was approximately 7 μm.
[0298] Example 4: Positive electrode layer (113.8 μm, Li₂S-LiI-CNF) / solid electrolyte layer (30 μm) / negative electrode layer (37 μm, Li-SiO₂) z (z=1.07) Particles:CNT=9:1 + binder)
[0299] The all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that a positive electrode containing a sulfide-based positive electrode active material was used and the elastic sheet was omitted.
[0300] (Manufacturing of the positive electrode)
[0301] The Li₂S-LiI-CNF composite prepared in Preparation Example 1 was used as the positive electrode active material. Li₆PS₅Cl (D₅₀ = 3.0 μm, crystalline) was prepared as a silcerium sulfide-germanium mineral-type crystal as the solid electrolyte. PTFE was prepared as a binder. A positive electrode mixture was prepared by mixing these materials at a weight ratio of composite positive electrode active material: solid electrolyte: binder = 60:40:1.2. The positive electrode mixture was obtained by mixing using a ball mill.
[0302] The positive electrode mixture was placed on the surface of a positive electrode current collector consisting of an aluminum foil with carbon coated on one surface, and the mixture was pressed at a pressure of 200 MPa for 10 minutes to fabricate the positive electrode. The total thickness of the positive electrode layer was approximately 113.8 μm. The thickness of the positive electrode active material layer was approximately 93.8 μm, and the thickness of the carbon-coated aluminum foil was approximately 20 μm.
[0303] The initial charge capacity of the positive electrode layer was measured using the aforementioned half-cell. The initial charge capacity of the positive electrode active material layer was measured using the half-cell. The initial charge capacity of the negative electrode was measured in the same manner as in Example 1.
[0304] In Example 4, the ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer to the initial charge capacity (A) of the positive electrode active material layer is 0.48. The initial charge capacity of the positive electrode active material layer is achieved by charging from a first open-circuit voltage to 2.8 V (relative to Li / Li). + The initial charge capacity of the first negative electrode active material layer is determined by charging from the second open-circuit voltage to 0.01 V (relative to Li / Li). + To determine.
[0305] In Examples 5 and 4 described below, measured under the same conditions as in Example 1, the ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer to the initial charge capacity (A) of the positive electrode active material layer was 0.49 and 0.55, respectively.
[0306] Example 5: Positive electrode layer (113.8 μm, Li₂S-LiI-CNF) / solid electrolyte layer (30 μm) / negative electrode layer (37 μm, Li-SiO₂) z (z=1.07) Particles:CNT=9:1 + binder):(Li-SiO z (Particles:Ag-C = 2:2 by weight)
[0307] The all-solid-state secondary battery was manufactured in the same manner as in Example 2, except that a positive electrode containing a sulfide-based positive electrode active material was used and the elastic sheet was omitted.
[0308] (Positive electrode manufacturing)
[0309] The Li₂S-LiI-CNF composite prepared in Preparation Example 1 was used as the positive electrode active material. A silicogermanium sulfide crystal, Li₆PS₅Cl, was prepared as the solid electrolyte (D₅₀ = 3.0 μm, crystalline). PTFE was prepared as the binder. These materials were mixed at a weight ratio of composite positive electrode active material: solid electrolyte: binder = 60:40:1.2 to prepare a positive electrode mixture. The positive electrode mixture was obtained by mixing using a ball mill.
[0310] The positive electrode mixture was placed on the surface of a positive electrode current collector consisting of an aluminum foil with carbon coated on one surface, and the mixture was pressed at a pressure of 200 MPa for 10 minutes to fabricate the positive electrode. The total thickness of the positive electrode layer was approximately 113.8 μm. The thickness of the positive electrode active material layer was approximately 93.8 μm, and the thickness of the carbon-coated aluminum foil was approximately 20 μm.
[0311] Example 6: Positive electrode layer (113.8 μm, Li₂S-LiI-CNF) / Solid electrolyte layer (30 μm) / Negative electrode layer (37 μm, Li-SiO₂) z (z=1.07) Particles:CNT=9:1 + binder):(Li-SiO z (z=1.07) Particles:Ag-loaded particles C=2:2 weight ratio)
[0312] The all-solid-state secondary battery was manufactured in the same manner as in Example 3, except that a positive electrode containing a sulfide-based positive electrode active material was used and the elastic sheet was omitted.
[0313] (Positive electrode manufacturing)
[0314] The Li₂S-LiI-CNF composite prepared in Preparation Example 1 was used as the positive electrode active material. A silicogermanium sulfide crystal, Li₆PS₅Cl, was prepared as the solid electrolyte (D₅₀ = 3.0 μm, crystalline). PTFE was prepared as the binder. These materials were mixed at a weight ratio of composite positive electrode active material: solid electrolyte: binder = 60:40:1.2 to prepare a positive electrode mixture. The positive electrode mixture was obtained by mixing using a ball mill.
[0315] The positive electrode mixture was placed on one surface of a positive electrode current collector formed by an aluminum foil with carbon coated on one surface, and the positive electrode was fabricated by plate pressing at a pressure of 200 MPa for 10 minutes. The total thickness of the positive electrode layer was approximately 113.8 μm. The thickness of the positive electrode active material layer was approximately 93.8 μm, and the thickness of the carbon-coated aluminum foil was approximately 20 μm.
[0316] The initial charge capacity of the positive electrode layer was measured using the aforementioned half-cell. The initial charge capacity of the positive electrode active material layer was measured using the half-cell. The initial charge capacity of the negative electrode was measured in the same manner as in Example 1.
[0317] Comparative Example 4: Elastic sheet (50 μm) / Positive electrode layer (113.8 μm, Li₂S-LiI-CNF) / Solid electrolyte layer (30 μm) / Negative electrode layer (37 μm, SiO₂) z (z=1.07) Particles:CNT=9:1 + binder)
[0318] The all-solid-state secondary battery was manufactured in the same manner as in Example 4, except that the negative electrode layer was manufactured according to the following method and an elastic sheet with a thickness of 50 μm was used.
[0319] (Manufacturing of the negative electrode layer)
[0320] A 10 μm thick SUS foil was prepared as the negative electrode current collector. SiO₂ with a D50 particle size of 4 μm was used. z (z=1.07) is used as the active material for the first negative electrode. SiO z (z=1.07) Purchased from Aldrich. Carbon nanotubes consist of primary and secondary structures. The primary structure is composed of a single carbon nanotube unit. The length of each unit is 200 nm–300 nm, and the diameter is approximately 5 nm–10 nm. The secondary structure is formed by the aggregation of multiple carbon nanotube units. The secondary structure is approximately 5 μm long and approximately 40 nm in diameter.
[0321] 2 g of Li-SiO₂ with a weight ratio of 9:1 z A mixture of (z=1.07) particles and carbon nanotubes was placed in a container with 2 g of a mixture of carbon black (CB) and silver (Ag) in a 3:1 weight ratio. 4 g of an NMP solution including 7 wt% PVDF binder (#9300 from Kureha Company) was added to prepare a mixed solution. The mixed solution was stirred to prepare a slurry while NMP was added little by little. The prepared slurry was coated onto an SUS substrate using a doctor blade coater, dried in air at 80°C for 10 minutes, and then vacuum dried at 40°C for 10 hours to prepare a laminate. The prepared laminate was cold-rolled to planarize the surface, thereby preparing a negative electrode with a first negative electrode active material layer / negative electrode current collector structure. The thickness of the first negative electrode active material layer was approximately 27 μm.
[0322] An elastic sheet (thickness: 50 μm) is further disposed on the positive electrode current collector of the pressed laminate.
[0323] Comparative Example 5: Elastic sheet (50 μm) / Positive electrode layer (13.8 μm, Li₂S-LiI₂CNF) / Solid electrolyte layer (30 μm) / Negative electrode layer (37 μm, SiO₂) z (z=1.07) Particles:CNT=9:1 + binder (SiO) z (Particles:Ag-C = 2:2 by weight)
[0324] The all-solid-state secondary battery was manufactured in the same manner as in Example 4, except that the negative electrode layer was manufactured according to the following method.
[0325] (Manufacturing of the negative electrode layer)
[0326] A 10 μm thick SUS foil was prepared as the negative electrode current collector. SiO₂ with a D50 particle size of 4 μm was used.z (z=1.07) is used as the active material for the first negative electrode. SiO z (x=1.07) Purchased from Aldrich. Carbon nanotubes consist of primary and secondary structures. The primary structure is composed of a single carbon nanotube unit. The length of each unit is 200 nm–300 nm, and its diameter is approximately 5 nm–10 nm. The secondary structure is formed by the aggregation of multiple carbon nanotube units. The secondary structure is approximately 5 μm long and has a diameter of approximately 40 nm.
[0327] 2 g of Li-SiO₂ with a weight ratio of 9:1 z A mixture of (z=1.07) particles and carbon nanotubes was placed in a container with 2 g of a mixture of carbon black (CB) and silver (Ag) in a 3:1 weight ratio. 4 g of an NMP solution containing 7 wt% PVDF binder (#9300 from Kureha Company) was added to prepare a mixed solution. A slurry was prepared by stirring the mixed solution while NMP was added little by little. The prepared slurry was coated onto an SUS substrate using a doctor blade coater, dried in air at 80°C for 10 minutes, and then vacuum dried at 40°C for 10 hours to prepare a laminate. The prepared laminate was cold-rolled to planarize the surface, thereby preparing a negative electrode with a first negative electrode active material layer / negative electrode current collector structure. The thickness of the first negative electrode active material layer was approximately 27 μm.
[0328] The initial charge capacity of the negative electrode is measured using the aforementioned half-cell.
[0329] Comparative Example 6: Elastic sheet (50 μm) / Positive electrode layer (113.8 μm, Li2S-LiI-CNF) / Solid electrolyte layer (30 μm) / Negative electrode layer (17 μm, Ag-C+ binder)
[0330] The all-solid-state secondary battery was manufactured in the same manner as in Example 4, except that the negative electrode prepared by the following method was used as the negative electrode layer and an elastic sheet with a thickness of 50 μm was used.
[0331] (Negative electrode manufacturing)
[0332] A 10 μm thick SUS foil was prepared as the negative electrode current collector. 4 g of carbon black (CB) and silver (Ag) in a 3:1 weight ratio were placed in a container, and 4 g of an NMP solution containing 7 wt% PVDF binder (#9300 from Kureha Company) was added to prepare a mixed solution. A slurry was prepared by stirring the mixed solution while NMP was added little by little. The prepared slurry was coated onto an SUS substrate using a doctor blade coater, dried in air at 80°C for 10 minutes, and then vacuum dried at 40°C for 10 hours to prepare a laminate. The prepared laminate was cold-rolled to planarize the surface, thereby preparing a negative electrode with a first negative electrode active material layer / negative electrode current collector structure. The thickness of the first negative electrode active material layer was approximately 7 μm.
[0333] An elastic sheet (thickness: 50 μm) is additionally placed on the positive electrode current collector of the pressed laminate.
[0334] Evaluation Example 1: Evaluation of volume changes during charging and discharging (NCA positive electrode active material)
[0335] For the all-solid-state secondary batteries prepared in Examples 1 and 2 and Comparative Example 3, the first cycle of charging was performed only in the charging and discharging experiments of Evaluation Example 2 below, and then scanning electron microscope images of the cross-section of the all-solid-state secondary battery were measured to observe the thickness change.
[0336] After the first charging cycle, a lithium metal layer is formed between the first negative electrode active material layer and the negative electrode current collector.
[0337] In the all-solid-state secondary batteries of Examples 1 and 2, the thickness of the lithium metal layer formed between the first negative electrode active material layer and the negative electrode current collector after initial charging is about 9 μm, which is less than the thickness of the first negative electrode active material layer of 28 μm after charging.
[0338] After the initial charging of the all-solid-state secondary batteries in Examples 1 and 2 (excluding the elastic member), the thickness increases to 10% or less of the initial thickness of the all-solid-state secondary batteries. As a result, volume changes during the charging and discharging processes of the all-solid-state secondary batteries in Examples 1 and 2 are suppressed.
[0339] In the all-solid-state secondary batteries of Examples 1 and 2, an elastic member with a thickness of 50 μm was used to accommodate volume changes during charging and discharging. As a result, the energy density of the all-solid-state secondary battery was reduced by including the elastic member.
[0340] After the initial charging of the all-solid-state secondary battery in Comparative Example 3, the thickness of the lithium metal layer formed between the first negative electrode active material layer and the negative electrode current collector was about 30 μm, which was greater than the thickness of the first negative electrode active material layer of 7 μm after charging.
[0341] After the initial charging of the all-solid-state secondary battery in Comparative Example 3 (excluding the elastic member), the thickness increased by more than 15% of the initial thickness of the all-solid-state secondary battery. As a result, the volume change was significant during the charging and discharging processes of the all-solid-state secondary battery in Comparative Example 3.
[0342] In the all-solid-state secondary battery of Comparative Example 3, an elastic member with a thickness of 100 μm was used to accommodate volume changes during charging and discharging. As a result, the energy density of the all-solid-state secondary battery was further reduced by including the elastic member with a thickness of 100 μm.
[0343] Evaluation Example 2: Evaluation of volume changes during charging and discharging (Li2S-LiI-CNF positive electrode active material)
[0344] For the all-solid-state secondary batteries prepared in Examples 4 and 5 and Comparative Example 6, only the first cycle of charging in the charge and discharge experiment of Evaluation Example 2 was performed, and then scanning electron microscope images of the cross-section of the all-solid-state secondary battery were measured to observe the thickness change. After the first cycle of charging, a lithium metal layer was formed between the first negative electrode active material layer and the negative electrode current collector.
[0345] In the all-solid-state secondary battery of Example 4, the thickness of the lithium metal layer formed between the first negative electrode active material layer and the negative electrode current collector after initial charging is approximately 9 μm, which is less than the 30 μm thickness of the first negative electrode active material layer after charging. In the all-solid-state secondary battery of Example 5, the thickness of the lithium metal layer formed between the first negative electrode active material layer and the negative electrode current collector after initial charging is approximately 9 μm, which is less than the 28 μm thickness of the first negative electrode active material layer after charging.
[0346] After initial charging, the thickness of the all-solid-state secondary batteries in Examples 4 and 5 increased to 7% or less of the initial thickness. As a result, the volume change during the charging and discharging processes of the all-solid-state secondary batteries in Examples 4 and 5 was not significant. In the all-solid-state secondary batteries of Examples 4 and 5, no elastic member was used to accommodate volume changes during charging and discharging. As a result, the energy density of the all-solid-state secondary batteries did not decrease due to the elastic member.
[0347] In the all-solid-state secondary battery prepared in Comparative Example 6, the thickness of the lithium metal layer formed between the first negative electrode active material layer and the negative electrode current collector after initial charging was approximately 30 μm, which is greater than the 7 μm thickness of the first negative electrode active material layer. After initial charging, the thickness of the all-solid-state secondary battery of Comparative Example 6, excluding the elastic member, increased by more than 10% of the initial thickness of the all-solid-state secondary battery. As a result, the volume change during the charging and discharging processes of the all-solid-state secondary battery of Comparative Example 6 was significant.
[0348] In the all-solid-state secondary battery of Comparative Example 6, an elastic member with a thickness of 50 μm was used to accommodate the increased volume change during charging and discharging. As a result, the energy density of the all-solid-state secondary battery was partially reduced by including the elastic member with a thickness of 50 μm.
[0349] Evaluation Example 3: Charge and Discharge Test
[0350] The charge and discharge characteristics of the all-solid-state secondary batteries manufactured in Examples 1-3 and Comparative Examples 1-2 were evaluated by the following charge and discharge tests. The all-solid-state secondary batteries were placed in a 45°C constant temperature bath for charge and discharge tests. In the first cycle, the batteries were charged at a constant current of 0.5 mA / cm² for 12.5 hours until the battery voltage reached 4.25V. Subsequently, the batteries were charged at a constant current of 0.5 mA / cm² for 12.5 hours. 2 Discharge at a constant current for 12.5 hours until the battery voltage reaches 2.5 V.
[0351] Meanwhile, the charge and discharge characteristics of the all-solid-state secondary batteries manufactured in Examples 4-6, Comparative Examples 4 and 5 were evaluated through the following charge and discharge tests. The all-solid-state secondary batteries were placed in a 45°C constant temperature bath for charge and discharge tests. In the first cycle, the battery was charged at a constant current of 0.1 C for 12.5 hours until the battery voltage reached 2.8V. Subsequently, it was discharged at a constant current of 0.1 C for 12.5 hours until the battery voltage reached 0.3V. The discharge capacity of the first cycle was defined as the standard capacity. After the first cycle, charge and discharge were performed under the same conditions as the first cycle until 850 cycles were completed. The measurement results are shown in Table 1 below.
[0352] Cycle count refers to the number of cycles required for the discharge capacity to drop to 80% of the standard capacity after the first cycle. A higher cycle count is generally considered to indicate better lifetime characteristics.
[0353] The initial efficiency is represented by Equation 1 below.
[0354] <Equation 1>
[0355] Initial efficiency (%) = [Discharge capacity in the first cycle / Charge capacity in the first cycle] × 100
[0356] [Table 1]
[0357]
[0358] Table 1 (continued)
[0359]
[0360] As shown in Table 1, the all-solid-state secondary batteries of Examples 1 and 2 exhibit superior initial efficiency and lifetime characteristics due to the suppression of volume changes during charging and discharging, and the suppression of the increase in internal resistance. Although not shown in Table 1, the all-solid-state secondary battery of Example 3 also exhibits improved initial efficiency and lifetime characteristics compared to the all-solid-state secondary battery of Comparative Example 3. It has been determined that the all-solid-state secondary batteries of Examples 1-3 have improved initial efficiency and lifetime characteristics compared to the all-solid-state secondary batteries of Comparative Examples 1 and 2 by including a first negative electrode active material of lithium-ionized silicon oxide.
[0361] As shown in Table 1, the all-solid-state secondary batteries of Examples 4 and 5 exhibit superior initial efficiency and lifetime characteristics by suppressing volume changes during charging and discharging and suppressing increases in internal resistance. Compared to the all-solid-state secondary batteries of Comparative Examples 4 and 5, the all-solid-state secondary batteries of Examples 4 and 5 demonstrate improved initial efficiency and lifetime characteristics by including a first negative electrode active material of lithium-ionized silicon oxide. Furthermore, although not shown in Table 1, the all-solid-state secondary battery of Example 6 also exhibits improved initial efficiency and lifetime characteristics compared to the all-solid-state secondary batteries of Comparative Examples 4 and 5.
[0362] Evaluation Example 4: Evaluation of High-Rate Characteristics
[0363] The high-rate characteristics of the all-solid-state secondary batteries of Examples 1-3 and Comparative Examples 1-3 were evaluated by the following charge-discharge tests. The solid-state secondary batteries were placed in a constant temperature bath at 45°C for charge-discharge tests.
[0364] The all-solid-state secondary batteries of Examples 1-3 and Comparative Examples 1-3 were charged with a constant current at 0.1 C rate at 45°C until the voltage reached 3.9 V (relative to Li), and then cut off with a current at 0.05 C rate while maintaining the voltage at 3.9 V in a constant voltage mode. Subsequently, after discharge, the battery was discharged with a constant current at 0.1 C rate until the voltage reached 2.5 V (relative to Li) (formation cycle). The all-solid-state secondary batteries that had undergone formation cycle were charged with a constant current at 0.2 C rate at 45°C until the voltage reached 3.9 V (relative to Li). Subsequently, after discharge, the battery was discharged with a constant current at 0.2 C rate until the voltage reached 2.5 V (relative to Li) (first cycle). The all-solid-state secondary batteries that had undergone the first cycle were charged with a constant current at 0.2 C rate at 45°C until the voltage reached 3.9 V (relative to Li). Subsequently, after discharge, the battery was discharged at a constant current rate of 0.33 C until the voltage reached 2.5 V (relative to Li) (second cycle). The all-solid-state rechargeable battery that had completed the second cycle was then charged at a constant current rate of 0.2 C at 45°C until the voltage reached 3.9 V (relative to Li). Subsequently, after discharge, the battery was discharged at a constant current rate of 0.5 C until the voltage reached 2.5 V (relative to Li) (third cycle). The all-solid-state rechargeable battery that had completed the third cycle was charged at a constant current rate of 0.2 C at 45°C until the voltage reached 3.9 V (relative to Li). Subsequently, after discharge, the battery was discharged at a constant current rate of 1.0 C until the voltage reached 2.5 V (relative to Li) (fourth cycle).
[0365] In all charge / discharge cycles, a 10-minute rest period was provided after each charge / discharge cycle. Furthermore, the high-rate characteristics of the all-solid-state secondary batteries of Examples 4, 5, and Comparative Examples 4-6 were evaluated through the following charge / discharge tests. The solid-state secondary batteries were placed in a constant-temperature bath at 45°C for the charge / discharge tests.
[0366] The all-solid-state secondary batteries of Examples 4 and 5, and Comparative Examples 4 to 6, were charged with a constant current at 0.1 C rate at 45°C until the voltage reached 2.5 V (relative to Li), and then cut off with a current at 0.05 C rate while maintaining the voltage at 2.5 V in a constant voltage mode. Subsequently, after discharge, the batteries were discharged with a constant current at 0.1 C rate until the voltage reached 0.3 V (relative to Li) (formation cycle). The all-solid-state secondary batteries that had undergone formation cycles were charged with a constant current at 0.2 C rate at 45°C until the voltage reached 2.5 V (relative to Li). Subsequently, after discharge, the batteries were discharged with a constant current at 0.2 C rate until the voltage reached 0.3 V (relative to Li) (first cycle). The all-solid-state secondary batteries that had undergone the first cycle were charged with a constant current at 0.2 C rate at 45°C until the voltage reached 2.5 V (relative to Li). Subsequently, after discharge, the battery was discharged at a constant current rate of 0.33 C until the voltage reached 0.3 V (relative to Li) (second cycle). The all-solid-state rechargeable battery that had completed the second cycle was then charged at a constant current rate of 0.2 C at 45°C until the voltage reached 2.5 V (relative to Li). Subsequently, after discharge, the battery was discharged at a constant current rate of 0.5 C until the voltage reached 0.3 V (relative to Li) (third cycle). The all-solid-state rechargeable battery that had completed the third cycle was charged at a constant current rate of 0.2 C at 45°C until the voltage reached 2.5 V (relative to Li). Subsequently, after discharge, the battery was discharged at a constant current rate of 1.0 C until the voltage reached 0.3 V (relative to Li) (fourth cycle).
[0367] A 10-minute rest period is provided after each charge / discharge cycle in all charge / discharge cycles. The high-rate characteristics of each all-solid-state secondary battery are defined by Equation 2 below.
[0368] Equation 2
[0369] High-rate performance [%] = [Discharge capacity at the fourth cycle / Discharge capacity at the formation cycle] × 100
[0370] [Table 2]
[0371]
[0372] Table 2 (continued)
[0373]
[0374] As shown in Table 2, the all-solid-state secondary batteries of Examples 1-2 exhibit improved high-rate characteristics compared to the all-solid-state secondary batteries of Comparative Examples 3, 1, and 2. Although not shown in Table 2, the all-solid-state secondary battery of Example 3 also exhibits improved high-rate characteristics compared to the all-solid-state secondary batteries of Comparative Examples 1-3. It is determined that the all-solid-state secondary batteries of Examples 1-3, which include a first negative electrode active material having lithium-modified silicon oxide, exhibit improved high-rate characteristics compared to the all-solid-state secondary batteries of Comparative Examples 1-3.
[0375] Furthermore, as shown in Table 2, compared with the all-solid-state secondary batteries of Comparative Examples 4 to 6, the all-solid-state secondary batteries of Examples 4 and 5, which include a first negative electrode active material of lithium-ionized silicon oxide, exhibit improved high-rate characteristics.
Claims
1. An all-solid-state secondary battery, comprising: positive electrode layer; negative electrode layer; and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, wherein the positive electrode layer comprises a positive electrode current collector and a positive electrode active material layer on one surface of the positive electrode current collector, the negative electrode layer comprises a negative electrode current collector and a first negative electrode active material layer on one surface of the negative electrode current collector, the first negative electrode active material layer comprises a first negative electrode active material and a carbon-based material, and the first negative electrode active material comprises lithium silicon oxide.
2. The all-solid-state secondary battery according to claim 1, wherein the lithium silicon oxide is a compound represented by Formula 1 below: Formula 1 Li x Yes y About z in, In Formula 1, 0<x≤4, 0<y≤5 and 0<z≤5.
3. The all-solid-state secondary battery as described in claim 2, wherein, In Formula 1, x is 1 to 4, y is 1 to 5, and z is 0.1 to 2.
4. The all-solid-state secondary battery as described in claim 1, wherein the lithium silicon oxide is Li-SiO z (0.5≤z≤2), Li4SiO4, Li2SiO3, Li2Si2O5 or combinations thereof.
5. The all-solid-state secondary battery according to claim 1, wherein the lithium silicon oxide further comprises magnesium, calcium or a combination thereof.
6. The all-solid-state secondary battery according to claim 5, wherein the lithium silicon oxide is a compound represented by Formula 2 below: Formula 2 Lee x (YOU) z1 (He / She) z ) in, In Formula 2, 0<x≤4, 0<y≤5, 0<z≤5, 2.2≤z1≤5.5, and M is Mg, Ca or a combination thereof.
7. The all-solid-state secondary battery according to claim 1, wherein the carbon-based material comprises a fibrous carbon-based material, the fibrous carbon-based material comprises a fibrous carbon nanostructure, the fibrous carbon nanostructure comprises carbon nanotubes, carbon nanofibers, carbon nanobelts or a combination thereof, and the content of the carbon-based material is 1 wt% to 50 wt% of the total weight of the first negative electrode active material and the carbon-based material.
8. The all-solid-state secondary battery according to claim 1, wherein the first negative electrode active material is in the form of particles, and the size of the first negative electrode active material is 0.1 μm to 30 μm.
9. The all-solid-state secondary battery according to claim 1, wherein the first negative electrode active material layer further comprises a second negative electrode active material, and the second negative electrode active material comprises a mixture of first particles composed of amorphous carbon and second particles composed of a second metal-based negative electrode active material, and based on the total weight of the mixture, the content of the second particles is 1 wt% to 60 wt%.
10. The all-solid-state secondary battery according to claim 1, wherein the first negative electrode active material layer further comprises a second negative electrode active material, and the second negative electrode active material comprises a composite negative electrode active material, wherein the composite negative electrode active material comprises a carbon-based carrier; and a third metal-based negative electrode active material supported on the carbon-based carrier, the third metal-based negative electrode active material comprises a metal, a metal oxide, a composite of a metal and a metal oxide, or a combination thereof, the third metal-based negative electrode active material is in the form of particles, the particle size of the third metal-based negative electrode active material is 1 nm to 200 nm, the carbon-based carrier is in the form of particles, and the particle size of the carbon-based carrier is 10 nm to 2 μm.
11. The all-solid-state secondary battery of claim 1, wherein the carbon material comprises a fibrous carbon material having an aspect ratio of 10 or greater, and the fibrous carbon material comprises amorphous fibrous carbon material, crystalline fibrous carbon material, or a combination thereof.
12. The all-solid-state secondary battery of claim 1, wherein the carbon material comprises a fibrous carbon nanostructure, and the fibrous carbon nanostructure comprises carbon nanotubes, carbon nanofibers, carbon nanoribbons, carbon nanorods, or combinations thereof.
13. The all-solid-state secondary battery of claim 1, wherein the first negative electrode active material layer further comprises a binder, wherein The adhesive includes polymeric adhesives, and the adhesive includes fluorinated adhesives.
14. The all-solid-state secondary battery as claimed in claim 1, wherein the ratio (B / A) of the initial charging capacity (B) of the first negative electrode active material layer to the initial charging capacity (A) of the positive electrode active material layer is 0.01 to 0.
75.
15. The all-solid-state secondary battery of claim 1, further comprising a second negative electrode active material layer disposed on at least one of the region between the negative electrode current collector and the first negative electrode active material layer and the region between the negative electrode current collector and the electrolyte layer. The second negative electrode active material layer is a metal layer, and the metal layer includes lithium or a lithium alloy.
16. The all-solid-state secondary battery of claim 1, wherein the positive electrode active material layer comprises a positive electrode active material. The positive electrode active material includes sulfide-based positive electrode active materials, oxide-based positive electrode active materials, or combinations thereof. The sulfide-based positive electrode active material includes nickel sulfide, copper sulfide, Li₂S, Li₂S-containing complexes, or combinations thereof, and The oxide-based positive electrode active material includes lithium transition metal oxides, metal oxides, or combinations thereof. The lithium transition metal oxides include lithium cobalt oxide, lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium iron phosphate, or combinations thereof. The lithium oxides include iron oxides, vanadium oxides, or combinations thereof.
17. The all-solid-state secondary battery of claim 1, wherein the positive electrode active material layer further comprises at least one selected from solid electrolyte, conductive material, and binder, and The solid electrolyte includes sulfide-based solid electrolytes, and the conductive material includes carbon-based conductive materials.
18. The all-solid-state secondary battery of claim 1, wherein the solid electrolyte layer comprises a solid electrolyte or a combination of a solid electrolyte and a gel electrolyte. The solid electrolyte includes sulfide solid electrolytes, oxide solid electrolytes, polymer solid electrolytes, or combinations thereof. The gel electrolyte includes a polymeric gel electrolyte. The sulfide-based solid electrolyte is selected from at least one of the following: Li₂S-P₂S₅; Li₂S-P₂S₅-LiX, where X is a halogen element; Li₂S-P₂S₅-Li₂O; Li₂S-P₂S₅-Li₂O-LiI; Li₂S-SiS₂; Li₂S-SiS₂-LiI; Li₂S-SiS₂-LiBr; Li₂S-SiS₂-LiCl; Li₂S-SiS₂-B₂S₃-LiI; Li₂S-SiS₂-P₂S₅-LiI; Li₂S-B₂S₃; Li₂S-P₂S₅-Z m S n Where m and n are positive numbers, and Z is one of Ge, Zn, and Ga; Li2S-GeS2; Li2S-SiS2-Li3PO4; Li2S-SiS2-Li p MO q Where p and q are positive numbers, and M is one of P, Si, Ge, B, Al, Ga, and In; Li 7-x PS 6-x Cl x , where 0≤x≤2; Li 7-x PS 6-x Br x , where 0≤x≤2; and Li 7-x PS 6-x I x where 0 ≤ x ≤ 2; The sulfide-based solid electrolytes include silver-germanium sulfide-type solid electrolytes. The sulfide-germanium ore type solid electrolyte includes at least one selected from Li6PS5Cl, Li6PS5Br, and Li6PS5I, and The density of the sulfosilgermanium ore type solid electrolyte is 1.5 g / cc to 2.0 g / cc.
19. The all-solid-state secondary battery of claim 1, wherein at least one of the positive electrode current collector and the negative electrode current collector comprises a base film and a metal layer disposed on one or both surfaces of the base film. The base film comprises a polymer, and the polymer comprises polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. The metal layer includes indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or alloys thereof.
20. The all-solid-state secondary battery of claim 1, further comprising a first inactive member disposed on at least one of the other surfaces of the positive electrode current collector and the other surface of the negative electrode current collector. The first inactive component is an elastic component.
Citation Information
Patent Citations
Cathode for lithium ion secondary battery, and lithium ion secondary battery
KR1020160064942A
